Filling microstructure and delivery method

By designing a filled fine structure with a frame portion and a clamping partition portion with a plurality of fine holes, and using a protective layer for lamination during transportation, the problems of damage and poor filling during transportation are solved, and efficient filling and excellent processability are achieved.

CN115210411BActive Publication Date: 2025-04-01FUJIFILM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180018793.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-06
Filing Date
2021-02-15
Publication Date
2025-04-01
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

The prior art is prone to damage the filling part or micropores during transportation, resulting in poor filling and deterioration of processability, which cannot effectively suppress damage and poor filling during transportation, while taking into account processability.

Method used

A filler fine structure is designed, including a frame portion arranged on the outer edge, a clamping partition portion has a plurality of fine holes, and a metal is filled in the fine holes of the clamping partition portion so that it directly contacts the frame portion. By providing a protective layer on the second metal portion and transporting it layered, the fine pores are protected and filling and processability are taken into account.

Benefits of technology

It effectively suppresses damage during transportation, ensures the integrity of the filling part, avoids the occurrence of poor filling, and improves processability, ensuring structural stability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115210411B_ABST
    Figure CN115210411B_ABST
Patent Text Reader

Abstract

The present invention provides a filled microstructure and a conveying method that suppress damage during conveyance, suppress poor filling, and take into account processability. The filled microstructure comprises: a first metal part having a frame part arranged at the outer edge; a spacer part arranged in an area surrounded by the frame part and having a plurality of pores; and a second metal part that fills the plurality of pores of the spacer part and is in direct contact with the frame part. The first metal part comprises a metal selected from valve metals. The spacer part comprises an oxide of a metal selected from valve metals, and the average diameter of the plurality of pores is less than 1 μm. The thickness of the portion of the second metal part that exists on the frame part is greater than 2 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a filled microstructure having a plurality of pores filled with metal and a method for conveying the filled microstructure, and more particularly to a filled microstructure having excellent conveyability, suppressing filling defects, and taking into account processability and a method for conveying the filled microstructure. Background Art

[0002] A structure in which a plurality of through holes provided in an insulating substrate are filled with a conductive material such as a metal is one of the fields that has attracted attention in nanotechnology in recent years, and is expected to be used as anisotropic conductive components, for example.

[0003] Anisotropic conductive components are inserted between electronic parts such as semiconductor elements and circuit boards, and electrical connection between the electronic parts and the circuit board can be achieved simply by applying pressure. Therefore, they are widely used as electrical connection components for electronic parts such as semiconductor elements and as inspection connectors for functional inspections.

[0004] In particular, the miniaturization of electronic parts such as semiconductor elements is remarkable. In the conventional methods such as direct connection to wiring substrates such as wire bonding, flip chip bonding and thermocompression bonding, the stability of the electrical connection of electronic parts cannot be fully guaranteed, so anisotropic conductive components have attracted much attention as electronic connection components.

[0005] For example, Patent Document 1 describes a method for producing a microstructure by forming a microstructure with a density of 10 million pieces / mm 2 The substrate has microporous through-holes with a density above 100, and a part of the microporous through-holes are filled with a substance other than the material of the substrate. In the method for manufacturing a microstructure of Patent Document 1, the substrate is aluminum oxide, and at least the following treatments are sequentially performed on the aluminum substrate: (A) a treatment for forming an oxide film having micropores by anodizing; (B) a treatment for removing aluminum from the oxide film obtained by the above-mentioned treatment (A); (C) a treatment for removing a part of the micropores existing in the oxide film of aluminum by penetrating the above-mentioned treatment (B); (D) a treatment for filling the micropores penetrated by the above-mentioned treatment (C) with a substance other than the oxide film; and (E) a surface smoothing treatment for smoothing the surface and back of the oxide film after the above-mentioned treatment (D) by chemical mechanical polishing.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-167023 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] In the method for manufacturing a microstructure of the above-mentioned patent document 1, a microstructure in which a substance other than the material of the substrate is filled in the micropore through-hole can be obtained. As described above, in the method for manufacturing a microstructure of the patent document 1, (D) a treatment of filling the through micropores with a substance other than the oxide film, and (E) a surface smoothing treatment of smoothing the surface and back of the oxide film after the above-mentioned (D) treatment by chemical mechanical polishing are implemented, but sometimes the above-mentioned (D) and the above-mentioned (E) treatment are not performed continuously, but after the above-mentioned (D), for example, after a prescribed time has passed by conveying, the above-mentioned (E) is implemented. In this case, the filling part or the micropores may be damaged during transportation. In addition, when the filling part is thickened in order to suppress damage to the filling part or the micropores during transportation, the surface smoothing process takes time due to the grinding treatment, and the processability is deteriorated. When the filling part is thinned in order to improve the processability, the filling into the micropores may be insufficient, and poor filling may occur. Furthermore, as described above, the filling portion or micropores may be damaged during transportation. Thus, there is currently no filled microstructure and transportation method that can suppress damage during transportation, suppress filling defects, and achieve both processability.

[0011] An object of the present invention is to provide a filled microstructure and a conveying method which can suppress damage during conveyance, suppress filling defects, and achieve both processability.

[0012] Means for solving technical problems

[0013] In order to achieve the above object, one embodiment of the present invention provides a filled microstructure, which comprises: a first metal part having a frame part arranged at the outer edge; a spacer part arranged in a region surrounded by the frame part and having a plurality of pores; and a second metal part filling the plurality of pores of the spacer part and directly contacting the frame part. The first metal part comprises a metal selected from valve metals, the spacer part comprises an oxide of a metal selected from valve metals, the average diameter of the plurality of pores is 1 μm or less, and the thickness of a portion of the second metal part existing on the frame part is 2 μm or more.

[0014] It is preferable that a thickness of a portion of the second metal portion that is present on the frame portion is 100 μm or less.

[0015] Preferably, the first metal portion is made of aluminum, and the spacer portion is made of an anodic oxide film of aluminum.

[0016] Preferably, the second metal portion is made of copper.

[0017] Another aspect of the present invention provides a method for transporting a filled microstructure by providing a protective layer on a second metal portion and stacking the protective layer for transport.

[0018] Effects of the Invention

[0019] According to the present invention, it is possible to obtain a filled microstructure that can achieve both good processability while suppressing damage during transportation and filling defects, and to obtain a transportation method that can suppress damage during transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic plan view showing an example of a filled microstructure according to an embodiment of the present invention.

[0021] Figure 2 This is a schematic cross-sectional view showing an example of a filled microstructure according to an embodiment of the present invention.

[0022] Figure 3 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0023] Figure 4 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0024] Figure 5 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0025] Figure 6 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0026] Figure 7 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0027] Figure 8 This is a schematic cross-sectional view showing one step of the first example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0028] Fig. 9 yes Figure 7 A plan view of the structure shown.

[0029] Fig.10 It is a magnified representation Fig. 9 Schematic plan view of region Q of the structure shown.

[0030] Fig.11 It is a magnified representation Fig. 9 Schematic cross-sectional view of region Q of the structure shown.

[0031] Fig.12 This is a schematic cross-sectional view showing one step of the second example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0032] Fig.13 This is a schematic cross-sectional view showing one step of the second example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0033] Fig.14 This is a schematic cross-sectional view showing one step of the second example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0034] Fig.15 This is a schematic cross-sectional view showing one step of the second example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0035] Fig.16 This is a schematic cross-sectional view showing one step of the second example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0036] Fig.17 This is a schematic cross-sectional view showing one step of the third example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0037] Fig.18 This is a schematic cross-sectional view showing one step of the third example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0038] Fig.19 This is a schematic cross-sectional view showing one step of the third example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0039] Fig. 20 This is a schematic cross-sectional view showing one step of the third example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0040] Fig.21 This is a schematic cross-sectional view showing one step of the third example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0041] Fig. 22 This is a schematic cross-sectional view showing one step of the fourth example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0042] Fig.23 This is a schematic cross-sectional view showing one step of the fourth example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0043] Fig.24 This is a schematic cross-sectional view showing one step of the fourth example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0044] Fig.25This is a schematic cross-sectional view showing one step of the fourth example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0045] Fig.26 This is a schematic cross-sectional view showing one step of the fourth example of the method for producing a filled microstructure according to the embodiment of the present invention.

[0046] Fig. 27 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0047] Fig.28 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0048] Fig.29 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0049] Fig.30 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0050] Fig.31 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0051] Fig.32 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0052] Fig.33 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0053] Fig.34 This is a schematic cross-sectional view showing one step of a method for producing a metal-filled microstructure according to an embodiment of the present invention.

[0054] Fig.35 It is a plan view showing an example of the structure of the metal-filled microstructure according to the embodiment of the present invention.

[0055] Fig.36 This is a schematic cross-sectional view showing an example of the structure of the metal-filled microstructure according to the embodiment of the present invention.

[0056] Fig.37 This is a schematic perspective view showing an example of a container used in the transport step according to the embodiment of the present invention.

[0057] Fig.38This is a schematic perspective view showing an example of a stacking method in a conveying step according to an embodiment of the present invention.

[0058] Fig.39 This is a schematic perspective view showing an example of a storage bag used in the transport step according to the embodiment of the present invention. DETAILED DESCRIPTION

[0059] Hereinafter, the filling microstructure and the delivery method of the present invention will be described in detail based on the preferred embodiments shown in the accompanying drawings.

[0060] In addition, the drawings described below are exemplary drawings for explaining the present invention, and the present invention is not limited to the drawings shown below.

[0061] In addition, the following "to" indicating a numerical range means that the numerical values ​​described on both sides are included. a is the value α b ~Value β c refers to ε a The range includes the value α b and the value β c The range of, if expressed in mathematical symbols, is α b ≤ε a ≤β c .

[0062] Unless otherwise specified, angles such as "orthogonal" include the error ranges generally allowed in the corresponding technical field. Also, regarding humidity and time, unless otherwise specified, they include the error ranges generally allowed in the corresponding technical field.

[0063] In a filled microstructure having a partition with multiple pores and filled with metal in the multiple pores, if a large amount of metal is filled in order to protect the pores during transportation, it takes time to fill the metal, and the amount of metal filled also increases, which increases the cost. In addition, due to the grinding treatment, the surface smoothing process takes time and the processability deteriorates. On the other hand, if the metal filling is reduced, the processability becomes better, but the possibility of damage during transportation becomes higher. In addition, if the through hole is not filled with sufficient metal, poor filling may occur. As a result of in-depth research, it was found that by setting the amount of metal filled within a certain range, the pores can be protected during transportation, and the filling and processability of the pores can be taken into account, thereby completing the present invention. The following is a specific description of the filled microstructure.

[0064] [An example of filling microstructure]

[0065] Figure 1 is a schematic plan view showing an example of a filled microstructure according to an embodiment of the present invention, Figure 2This is a schematic cross-sectional view showing an example of a method for producing a filled microstructure according to an embodiment of the present invention.

[0066] Figure 1 The filled microstructure 10 shown comprises: a first metal part 15 having a frame part 15d arranged at an outer edge 15b; a spacer part 16 arranged in an area 15c surrounded by the frame part 15d and having a plurality of pores; and a second metal part 19 filling the plurality of pores (through holes 17) of the spacer part 16 and in direct contact with the frame part 15d.

[0067] In the filled microstructure 10, the frame portion 15d is disposed on the outer edge 15b of the bottom 15e of the first metal portion 15. The spacer 16 is disposed in a region 15c surrounded by the frame portion 15d. The first metal portion 15 will be described later.

[0068] As described above, the spacer 16 has a plurality of pores (through holes 17). The spacer 16 contains an oxide of a metal selected from valve metals and contained in the first metal part 15, and the average diameter of the plurality of pores (through holes 17) is 1 μm or less. The spacer 16 is composed of, for example, an oxide of the first metal part 15. The spacer 16 will be described later.

[0069] Frame 15d exists around spacer 16, and surface 16a of spacer 16 is substantially flush with the upper surface of frame 15d. Spacer 16 has electrical insulation, for example, and constitutes an insulating base material in the metal-filled microstructure.

[0070] In addition, being substantially on the same plane means that the height difference between the two planes is less than 200 μm.

[0071] The second metal part 19 is provided so as to exceed the surface 16a of the sandwiching part 16 and is also formed directly on the frame part 15d. The second metal part 19 is also filled between the sandwiching part 16 and the inner surface 15f of the frame part 15d of the first metal part 15 and is in direct contact with the inner surface 15f. Furthermore, the second metal part 19 is also in direct contact with the bottom surface 15g of the first metal part 15 on the opposite side of the surface 16a of the sandwiching part 16.

[0072] In addition, directly formed and directly contacting refer to a state in which there are no members or layers other than the two members between the two members.

[0073] The thickness of the second metal portion 19 on the frame portion 15d is 2 μm or more. To fill the through-hole 17 with metal, the thickness γ of the second metal portion 19 on the surface 16a of the intervening portion 16 is smaller than the thickness δ on the frame portion 15d.

[0074] The upper limit of the thickness δ of the portion of the second metal portion 19 existing on the frame portion 15d is, for example, 100 μm. The thickness δ of the portion existing on the frame portion 15d is also referred to as the thickness δ on the frame portion 15d.

[0075] If the thickness δ of the second metal portion 19 is greater than 2 μm, the spacers 16 and the frame 15 d are protected, and damage to the spacers 16 and the frame 15 d can be suppressed when the filled microstructure 10 is transported. Damage to the spacers 16 during transport, such as damage to the spacers 16 , can be suppressed.

[0076] Furthermore, if the thickness δ of the second metal portion 19 is 2 μm or more, preferably 100 μm or less, the through hole 17 of the spacer 16 can be sufficiently filled with metal, and the occurrence of poor filling can be suppressed. In addition, when the second metal portion 19 is polished and smoothed, the time required for polishing is shortened, and the processability is excellent.

[0077] As described above, when the thickness δ of the second metal portion 19 is 2 μm or more, preferably 100 μm or less, damage during transportation and poor filling into the through-hole 17 can be suppressed, and workability of the second metal portion 19 can be achieved.

[0078] In addition, the thickness δ of the second metal portion 19 is more preferably 2 to 20 μm, and further preferably 5 to 10 μm. If the thickness δ of the second metal portion 19 is within the above range, damage during transportation can be suppressed, and the transportability is excellent, and poor filling of the through hole 17 can be suppressed, and the time required for grinding, etc. can be further shortened, and the processability is more excellent.

[0079] The thickness δ of the second metal portion 19 on the frame portion 15 d is an average value measured at 10 points by cutting the filled microstructure 10 in the thickness direction and observing the cross section using a FE-SEM (Field emission-Scanning Electron Microscope).

[0080] The thickness γ of the surface 16 a of the intervening portion 16 of the second metal portion 19 is an average value measured at 10 points by cutting the filled microstructure 10 in the thickness direction and observing the cross section using FE-SEM.

[0081] The thickness of the bottom 15 e of the first metal portion 15 , that is, the thickness of the first metal portion 15 below the spacer 16 is not particularly limited, but is preferably 20 μm or more, and more preferably 30 to 50 μm.

[0082] The thickness of the bottom 15e of the first metal portion 15 is the average value of measurements taken at 10 points by cutting the filled microstructure 10 in the thickness direction and observing the cross section using FE-SEM, similarly to the thickness δ on the frame portion 15d of the second metal portion 19.

[0083] [First Example of Method for Producing Filled Microstructure]

[0084] Figure 3 to Figure 8 Schematic cross-sectional views showing a first example of a method for producing a filled microstructure according to an embodiment of the present invention in order of steps. Fig. 9 yes Figure 7 The plan view of the structure shown, Fig.10 It is a magnified representation Fig. 9 A schematic plan view of a region Q of the structure shown, Fig.11 It is a magnified representation Fig. 9 A schematic cross-sectional view of region Q of the structure shown. In addition, Figure 3 to Figure 11 In, with Figure 1 and Figure 2 The same components as shown are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0085] The first metal portion 15 filling the microstructure 10 includes a metal selected from valve metals, and for example, a valve metal member is used. In this case, the spacer 16 filling the microstructure 10 is an anodic oxide film obtained by anodizing the surface of the valve metal member.

[0086] For example, the filled microstructure has an insulating substrate composed of an anodic oxide film of a valve metal. The valve metal as the first metal part 15 is, for example, aluminum, but the valve metal is not particularly limited to aluminum. However, as an insulating substrate, an anodic oxide film of aluminum is used as an example. Therefore, in the following description, the first metal part 15 uses a valve metal component, and an aluminum substrate is used as an example.

[0087] like Figure 3 As shown, an aluminum substrate is prepared as the valve metal member 11 .

[0088] Then, if Figure 4As shown, the mask 12 is formed only on the outer edge 11b of the surface 11a of the valve metal part 11. The mask 12 is not particularly limited as long as it is an electrically insulating mask, and for example, a known resist film used to form a semiconductor element can be used. For the mask 12, for example, after forming a resist film on the entire surface 11a of the valve metal part 11, the resist film other than the outer edge 11b of the surface 11a of the valve metal part 11 is removed by photolithography, and the mask 12 is formed only on the outer edge 11b. In addition, as the mask 12, for example, a resist pen can be used to form a resist film only on the outer edge 11b of the surface 11a of the valve metal part 11. In addition, an acid-resistant adhesive resin tape can be attached to the outer edge 11b of the surface 11a of the valve metal part 11 as the mask 12.

[0089] In the surface 11a of the valve metal member 11, a region 11c surrounded by the mask 12 is an anodized film 11d (refer to Figure 5 ) formation area.

[0090] Next, an anodic oxide film forming step is performed, in which an anodic oxide treatment is performed using the valve metal member 11 as an electrode, and the region 11c of the valve metal member 11 surrounded by the mask 12 is formed into an anodic oxide film. The anodic oxide film is an insulating base material. The first metal portion 15 is obtained by performing an anodic oxide treatment on the valve metal member 11.

[0091] In the anodic oxide film forming step, the valve metal component 11 is used as an anode electrode and an anodic oxidation treatment is performed. As a result, the valve metal component 11 is anodized. Figure 3 As shown, an anodic oxide film 11d is formed on the region 15c of the first metal portion 15. In the anodic oxidation treatment, for example, current may be applied from the back side of the valve metal member 11 or from the outer edge 11b side.

[0092] In the anodizing treatment, as described above, the valve metal member 11 (reference Figure 4 ) as an electrode, the valve metal component 11 (reference Figure 4 ) becomes the formation area of ​​the anodized film 11d, and the valve metal member 11 (reference Figure 2 ) is the outer edge 15b of the first metal portion 15, which becomes the frame portion 15d.

[0093] The anodized film 11d is formed in the region 11c, but the valve metal member 11 below the mask 12 is not anodized. Thus, the entire valve metal member 11 is not formed into the anodized film 11d, and a region of the valve metal member 11 remains even after the anodizing process.

[0094] Thus, the frame portion 15d of the first metal portion 15 formed of the valve metal member 11 is disposed on the outer edge 15b of the first metal portion 15. The anodic oxide film 11d is formed in the region 15c surrounded by the frame portion 15d (see Figure 3 ) as the spacer 16.

[0095] In addition, since the valve metal member 11, that is, the first metal portion is made of aluminum, an anodic oxide film 11d is formed as an oxide film, and the anodic oxide film 11d is made of an Al2O3 film.

[0096] The anodized film 11d has a plurality of micropores when it is formed. However, among the plurality of micropores, there are also micropores that do not penetrate in the thickness direction Dt. In addition, there is a barrier layer (not shown) at the bottom of the micropores. Figure 3 The anodized film 11d shown in FIG. 1 is removed from the barrier layer. Figure 4 As shown, a plurality of through holes 17 extending in the thickness direction Dt are formed in the anodized film 11d, thereby obtaining a sandwich portion 16 constituted by the anodized film 11d.

[0097] Through the above steps, the spacer 16 (anodized film) having a plurality of pores (through holes 17) is formed in the region 15c surrounded by the frame portion 15d disposed on the outer edge 15b of the first metal portion 15, thereby obtaining a structure 18 having the first metal portion 15 and the spacer 16 (anodized film). Figure 4 and Fig.11 As shown in FIG. 1 , a spacer 16 (anodized film) is formed on the surface 15a of the first metal portion 15, and a frame portion 15d exists around the spacer 16. Fig.11 As shown, the surface 16a of the spacer portion 16 is substantially flush with the upper surface of the frame portion 15d.

[0098] As mentioned above, Figure 3 The anodized film forming process shown in Figure 4 The step of forming the plurality of through holes 17 extending in the thickness direction Dt is a step of obtaining the structure 18 .

[0099] 〔Aluminum substrate〕

[0100] The aluminum substrate used as a valve metal component is not particularly limited. Specific examples include: pure aluminum plates; alloy plates with aluminum as the main component and containing trace amounts of heterogeneous elements; substrates with high-purity aluminum vapor-deposited on low-purity aluminum (such as recycled materials); substrates with high-purity aluminum coated on the surfaces of silicon wafers, quartz, glass, etc. by vapor deposition, sputtering, etc.; resin substrates laminated with aluminum; etc.

[0101] In the aluminum substrate, the aluminum purity of the surface on the side where the anodized film is formed by anodizing treatment is preferably 99.5 mass % or more, more preferably 99.9 mass % or more, and further preferably 99.99 mass % or more. If the aluminum purity is within the above range, the regularity of the micropore arrangement becomes sufficient.

[0102] The aluminum substrate is not particularly limited as long as an anodized film can be formed, and for example, JIS (Japanese Industrial Standards) 1050 materials and 1070 materials can be used.

[0103] The surface of the aluminum substrate on the side to be anodized is preferably subjected to heat treatment, degreasing treatment, and mirror finishing treatment in advance.

[0104] Here, regarding the heat treatment, degreasing treatment, and mirror finishing treatment, the same treatments as those described in paragraphs

[0044] to

[0054] of Japanese Patent Application Laid-Open No. 2008-270158 can be performed.

[0105] The mirror finishing treatment before the anodizing treatment is, for example, electrolytic polishing, and the electrolytic polishing uses, for example, an electrolytic polishing liquid containing phosphoric acid.

[0106] 〔Anodizing process〕

[0107] A conventionally known method can be used for the anodizing treatment, but a self-regularization method or a constant voltage treatment is preferably used from the viewpoint of improving the regularity of the micropore arrangement and ensuring the anisotropic conductivity of the metal-filled microstructure.

[0108] Here, regarding the self-regulation method and constant pressure treatment of the anodizing treatment, the same method as in paragraphs

[0056] to

[0108] and [ Figure 3 ] are the same processing as the processing described in ].

[0109] In the anodized film having a plurality of micropores, as described above, a barrier layer (not shown) exists at the bottom of the micropores, and a barrier layer removal step of removing the barrier layer is provided.

[0110] [Barrier layer removal process]

[0111] The barrier layer removal step is a step of removing the barrier layer of the anodized film using, for example, an alkaline aqueous solution containing ions of the metal M1 having a higher hydrogen overvoltage than aluminum.

[0112] The barrier layer is removed by the barrier layer removal step, and a conductive layer made of the metal M1 is formed at the bottom of the microhole.

[0113] Here, hydrogen overvoltage refers to the voltage required to generate hydrogen gas, and for example, the hydrogen overvoltage of aluminum (Al) is -1.66 V (Journal of the Chemical Society of Japan, 1982, (8), p1305-1313). In addition, the following shows an example of a metal M1 having a higher hydrogen overvoltage than aluminum and its hydrogen overvoltage value.

[0114] <Metal M1 and hydrogen (1N H2SO4) overvoltage>

[0115] Platinum (Pt): 0.00V

[0116] Gold (Au): 0.02V

[0117] Silver (Ag): 0.08V

[0118] Nickel (Ni): 0.21V

[0119] Copper (Cu): 0.23V

[0120] Tin (Sn): 0.53V

[0121] Zinc (Zn): 0.70V

[0122] The through hole 17 (pore) can also be formed by expanding the diameter of the micropore and removing the barrier layer. In this case, the expansion of the micropore is performed by a pore expansion process. The pore expansion process is a process for expanding the pore diameter of the micropore by immersing the anodized film in an acidic aqueous solution or an alkaline aqueous solution to dissolve the anodized film. The pore expansion process can use an aqueous solution of an inorganic acid such as sulfuric acid, phosphoric acid, nitric acid, hydrochloric acid, or a mixture thereof, or an aqueous solution of sodium hydroxide, potassium hydroxide, lithium hydroxide, etc.

[0123] In addition, the barrier layer at the bottom of the micropores can also be removed during the pore expansion treatment. By using a sodium hydroxide aqueous solution in the pore expansion treatment, the micropores can be expanded in diameter and the barrier layer can be removed.

[0124] The hole expansion process cannot form a conductive layer in the same way as the barrier layer removal process. Therefore, after the hole expansion process, the conductive layer can be formed by treating again with an aqueous solution containing ions of the metal M1 having a higher hydrogen overvoltage than aluminum, or by performing multiple stages of treatment with aqueous solutions containing different metals.

[0125] Next, from Figure 6 Remove the mask 12 (reference Figure 7 ). And, for Figure 7 The structure 18 shown in the figure is subjected to a filling process of filling the plurality of through holes 17 of the sandwiching part 16 with metal. Figure 8As shown, for the structure 18, the second metal part 19 is formed by filling the inside of the plurality of through holes 17 of the spacer 16 with metal exceeding the surface 16a of the spacer 16. Thus, the filled microstructure 10 is obtained. In this case, the conductive path 20 having conductivity is formed by forming the second metal part 19. In addition, the filling process of the filling metal will be described in detail later.

[0126] In the filling process, metal is filled inside the plurality of through holes 17 of the sandwiching portion 16, and as shown in FIG. Figure 8 As shown in FIG. 1 , the second metal portion 19 is formed on the surface of the structure 18, that is, on the frame portion 15d of the microstructure 10 and the surface 16a of the sandwich portion 16, so that the metal is filled in the plurality of through holes 17. In this case, as described above, the thickness δ (refer to FIG. 1 ) of the portion of the second metal portion 19 existing on the frame portion 15d is Figure 2 ) is formed to be 2 μm or more. As described above, the upper limit of the thickness δ of the portion of the second metal portion 19 that is present on the frame portion 15d is, for example, 100 μm.

[0127] In addition, for example, by extending the plating time, the thickness δ of the second metal portion 19 can be increased. In the filling step, the second metal portion 19 is formed also on the frame portion 15d by filling the metal beyond the surface 16a of the spacer portion 16.

[0128] 〔Filling process〕

[0129] <Filling Metal>

[0130] The metal as the conductive material filled in the through hole 17 preferably has a resistivity of 10 3 As specific examples of materials with a resistance of Ω·cm or less, preferably gold (Au), silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), nickel (Ni), and zinc (Zn) are exemplified.

[0131] In addition, as the conductive material, from the viewpoint of conductivity, Cu, Au, Al, and Ni are preferred, Cu and Au are more preferred, and Cu is further preferred.

[0132] <Filling method>

[0133] As a plating method for filling the inside of the through hole with metal, for example, an electroplating method or an electroless plating method can be used.

[0134] Here, in the conventionally known electroplating method used for coloring, it is difficult to selectively precipitate (grow) metal in the hole with a high aspect ratio. The reason is believed to be that even if the precipitated metal is consumed in the hole and electrolysis is performed for a certain period of time or more, the plating layer will not grow.

[0135] Therefore, when metal is filled by plating, a pause time needs to be set during pulse electrolysis or constant potential electrolysis. The pause time needs to be 10 seconds or more, preferably 30 to 60 seconds.

[0136] Furthermore, it is also preferable to apply ultrasonic waves in order to promote stirring of the electrolyte solution.

[0137] In addition, electrolysis voltage is generally below 20V, and expectation is below 10V, but preferably measures the precipitation potential of the target metal in the employed electrolytic solution in advance, and carries out constant potential electrolysis in this potential+1V.In addition, when carrying out constant potential electrolysis, expectation can use cyclic voltammetry simultaneously, can use the constant potential instrument device of Solartron company, BAS Inc., HOKUTODENKO CORPORATION, IVIUM company etc.

[0138] In the above-mentioned electroplating method, constant current electrolysis can also be used, but it is preferred that the current value is set so that the voltage during electrolysis is within the same range as the above-mentioned electrolysis voltage. In this case, a common DC power supply can be used, for example, a known device of Matsusada Precision Inc., TAKASAGO, LTD., KIKUSUI ELECTRONICS CORP., TEXIO TECHNOLOGY CORPORATION, etc. can be used. In addition, in the above-mentioned electroplating method, pulse electrolysis commonly used in plating treatment can also be used.

[0139] As the plating solution, a conventionally known plating solution can be used.

[0140] Specifically, when copper is precipitated, an aqueous solution containing copper sulfate is generally used, but the concentration of copper sulfate is preferably 1 to 300 g / L, more preferably 100 to 200 g / L. Furthermore, if hydrochloric acid is added to the electrolyte, precipitation can be promoted. In this case, the concentration of hydrochloric acid is preferably 10 to 20 g / L.

[0141] Furthermore, the plating solution may contain an acid, and the acid concentration is preferably 0.01 to 1 mol / L.

[0142] An additive may be added to the electrolyte solution. Examples of the additive to be added to the electrolyte solution are shown below. The additive may provide the following effects.

[0143] As additives, additional components called brighteners and smoothing agents may be added.

[0144] In the adhesion inhibition effect, molecules or ions are adsorbed or precipitated alone to inhibit the plating reaction. Saccharin, benzothiazole, thiourea, Janus Green B (JGB), benzyl acetone, lead, bismuth, etc. correspond to components having an adhesion inhibition effect.

[0145] In the interfacial complex formation, a small amount of complex-forming ions adsorbed on the surface coordinate with metal ions to form ion bridges or electric bridges, thereby promoting the precipitation reaction. Chloride ions, CN-, SCN-, sulfur compounds (thiourea, 3,3'-dithiobis(1-propanesulfonic acid) disodium (SPS), dithiothiazole (DMTD), etc.), boric acid, oxalic acid, malonic acid, etc. are believed to correspond to this.

[0146] In the film formation, surfactants or polymers gently adhere to the plating surface to form a film and inhibit the plating reaction. Representative examples include PEG (polyethylene glycol), polyethylene glycol mono-4-nonylphenyl ether (PEGNPE), polyvinyl alcohol, gelatin, etc.

[0147] In the electrolytic consumption mechanism, molecules or ions are rapidly electrolytically reduced on the plating surface, and the reaction rate is determined by the diffusion and transport of these molecules or ions to the surface. As a result, the unevenness of the plating surface shape is reduced. Representative examples include unsaturated alcohols (butynediol, propargyl alcohol, coumarin, etc.), NO3 - , Fe 3+ wait.

[0148] Furthermore, the surface tension of the plating solution is preferably adjusted to be as low as possible, and the surface tension is preferably 60 mN / m or less, which is lower than that of pure water. A surfactant or an organic solvent may also be added to adjust the surface tension.

[0149] The pH (hydrogen ion index) of the plating solution is preferably adjusted, and the pH is preferably 1 or more.

[0150] When gold is to be deposited, it is preferred to perform plating by alternating current electrolysis using a sulfuric acid solution of tetrachlorogold.

[0151] Furthermore, in the electroless plating method, it takes a long time to completely fill the hole consisting of the through-hole having a high aspect ratio with the metal, and therefore it is preferable to fill the through-hole with the metal by using the electroless plating method.

[0152] Furthermore, by processing the filled fine-structure body 10 , a metal-filled fine-structure body described later can be obtained.

[0153] [Second Example of Method for Producing Filled Microstructure]

[0154] Figure 12 to Figure 16 2 is a schematic cross-sectional view showing a second example of a method for manufacturing a filled microstructure according to an embodiment of the present invention in order of steps. Figure 12 to Figure 16In, with Figure 1 and Figure 2 The same components as shown are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0155] The second example of the method for manufacturing a filled microstructure is different from the first example of the method for manufacturing a filled microstructure in that the mask 12 is not formed only on the outer edge 11b of the surface 11a of the valve metal member 11 (see Figure 4 ), but instead, the mask 13 having the opening 13a is arranged on the outer edge 11b of the surface 11a of the valve metal component 11. Except for this, a filled microstructure can be obtained in the same manner as the first example of the method for manufacturing a filled microstructure.

[0156] like Fig.12 As shown in FIG. 1 , a mask 13 having an opening 13a is disposed on the surface 11a of the valve metal member 11. Fig.13 As shown in FIG. 1 , a mask 13 is provided on the outer edge 11b of the surface 11a of the valve metal member 11. In this case, on the surface 11a of the valve metal member 11, a region 11c corresponding to the opening 13a of the mask 13 is an anodized film 11d (see FIG. 1 ). Fig.14 ) formation area.

[0157] Next, an anodic oxide film forming step is performed in which an anodic oxidation treatment is performed using the valve metal component 11 as an electrode, and the region 11c of the valve metal component 11 surrounded by the mask 13 is formed as an anodic oxide film. The anodic oxide film forming step is the same as the first example of the manufacturing method of the filled microstructure, and therefore a detailed description thereof is omitted. In the anodic oxide film forming step, an anodic oxide film 11d is formed in the region 11c, but the valve metal component 11 below the mask 13 is not anodized.

[0158] like Fig.15 As shown, after the anodizing treatment, the mask 13 is separated from the surface 11a of the valve metal member 11. Fig.15 The anodized film 11d shown in FIG. 1 is removed from the barrier layer. Fig.16 As shown, a plurality of through holes 17 extending in the thickness direction Dt are formed in the anodized film 11d, thereby obtaining a sandwich portion 16 constituted by the anodized film 11d.

[0159] Next, for Fig.16 The structure 18 shown in the figure is subjected to a filling process of filling the plurality of through holes 17 of the intervening portion 16 with metal. Figure 8As shown, for the structure 18, the second metal part 19 is formed by filling the inside of the plurality of through holes 17 of the partition 16 with metal exceeding the surface 16a of the partition 16. Thus, the filled microstructure 10 is obtained. The method for forming the second metal part 19 is the same as the first example of the manufacturing method of the filled microstructure, so its detailed description is omitted.

[0160] [Third Example of Method for Producing Filled Microstructure]

[0161] Figures 17 to 21 1 is a schematic cross-sectional view showing a third example of a filled microstructure according to an embodiment of the present invention in order of steps. Figures 17 to 21 In, with Figure 1 and Figure 2 The same components as shown are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0162] The third example of the method for manufacturing a filled microstructure is different from the first example of the method for manufacturing a filled microstructure in that the entire surface 11a of the valve metal part is anodized and the anodized film is removed to form a frame portion. Other than this, a filled microstructure can be obtained in the same manner as the first example of the method for manufacturing a filled microstructure.

[0163] In the third example of the method for manufacturing a filled microstructure, the valve metal component 11 is prepared in the same manner as in the first example of the method for manufacturing a filled microstructure (see Figure 3 ). Next, the entire surface 11a of the valve metal member 11 is anodized, leaving the bottom 11e of the valve metal member 11 (refer to Fig.17 ) to form an anodic oxide film 11d (reference Figure 5 ). In addition, with respect to the anodized film 11d, the barrier layer is removed, such as Fig.17 As shown, a plurality of through holes 17 extending in the thickness direction Dt are formed in the anodized film 11d, thereby obtaining a sandwich portion 16 composed of the anodized film. The valve metal member 11 (see Figure 3 ) is a bottom 11e of a portion thereof, the bottom 11e being the bottom 15e of the first metal portion 15. The spacer portion 16 preferably has a thickness H A Less than 200μm. If the thickness H A When the thickness is less than 200 μm, it can be considered that the spacer portion 16 and the first metal portion 15 are on the same plane.

[0164] Then, if Fig.18As shown, on the surface 16a of the sandwiching part 16, in addition to the outer edge 16e of the sandwiching part 16, a mask 14 is also arranged. In this state, the outer edge 16e of the sandwiching part 16 is dissolved by using a liquid having the property of dissolving the sandwiching part 16, such as the anodized film, and not dissolving the valve metal part 11. Fig.19 As shown, the bottom 15e of the first metal portion 15 is exposed.

[0165] The mask 14 is not particularly limited as long as it is insoluble in a liquid having the property of dissolving the spacer 16 and not dissolving the valve metal member 11. For example, a resist film is used. The resist film used for the mask 14 can be formed by forming a resist film on the entire surface 16a of the spacer 16 and then removing the resist film on the outer edge 16e of the spacer 16 by photolithography.

[0166] As the liquid having the property of dissolving the spacer 16 such as the anodic oxide film and not dissolving the valve metal member, an acidic aqueous solution or an alkaline aqueous solution that dissolves aluminum oxide (Al2O3) can be used. Specifically, for example, a hydrochloric acid aqueous solution containing cupric chloride can be used.

[0167] Then, if Fig. 20 As shown, the mask 14 is removed from the surface 16a of the intervening portion 16. Thus, a structure 18 including the first metal portion 15 and the intervening portion 16 (anodized film) is obtained.

[0168] The difference between the surface 16a of the spacer 16 and the upper surface of the frame portion 15d, that is, the thickness H of the spacer 16 A Therefore, the surface 16a of the spacer 16 is substantially flush with the upper surface of the frame portion 15d.

[0169] In addition, if the mask 14 is a resist film, for example, it can be removed by using ashing.

[0170] Next, for Fig. 20 The structure 18 shown in the figure is subjected to a filling process of filling the plurality of through holes 17 of the sandwiching part 16 with metal. Fig.21 As shown, for the structure 18, the second metal part 19a is formed by filling the inside of the plurality of through holes 17 of the spacer 16 with metal exceeding the surface 16a of the spacer 16. Thus, the filled microstructure 10 is obtained. In this case, by forming the second metal part 19a, a conductive path 20 having conductivity is formed. The method for forming the second metal part 19a is the same as the method for forming the second metal part 19 of the first example of the manufacturing method of the filled microstructure, and therefore its detailed description is omitted.

[0171] In addition, the mask 14 is disposed and the outer edge 16e of the sandwich portion 16 is dissolved, but the invention is not limited thereto, and the outer edge 16e of the sandwich portion 16 may be physically cut by grinding or laser or the like. Furthermore, the outer edge 16e of the sandwich portion 16 may be selectively dissolved by spraying a liquid having the property of, for example, dissolving the anodic oxide film but not dissolving the valve metal member onto the outer edge 16e of the sandwich portion 16 by an inkjet method.

[0172] [Fourth Example of Method for Producing Filled Microstructure]

[0173] Figure 22 to Figure 26 1 is a schematic cross-sectional view showing a fourth example of a method for manufacturing a filled microstructure according to an embodiment of the present invention in order of steps. Figure 22 to Figure 26 In, with Figure 1 and Figure 2 The same components as shown are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0174] The fourth example of the method for manufacturing a filled microstructure is different from the first example of the method for manufacturing a filled microstructure in that the valve metal part 11 is anodized using an electrode body 60 on which a conductive layer 62 having conductivity is locally formed on the surface 61a of an insulating support body 61. Other than this, a filled microstructure can be obtained in the same manner as in the first example of the method for manufacturing a filled microstructure.

[0175] In the fourth example of the method for manufacturing a filled microstructure, Fig. 22 As shown, first, an electrode body 60 is prepared in which a conductive layer 62 having conductivity is partially formed on a surface 61a of a rectangular insulating support body 61. The electrode body 60 is used as an electrode during anodizing treatment.

[0176] The conductive layer 62 forms a resist layer 63 on the surface 61a of the insulating support 61, and the resist layer 63 is partially removed by patterning using, for example, photolithography. Next, a seed layer (not shown) is formed on the resist layer 63, for example, and the conductive layer 62 is formed by plating. When the conductive layer 62 is formed, the surfaces of the resist layer 63 and the conductive layer 62 are flattened by a flattening treatment. In addition, the conductive layer 62 is formed by plating, but the method for forming the conductive layer 62 is not particularly limited.

[0177] Then, if Fig.23 As shown in FIG. 1 , a valve metal member 11 is provided to cover a conductive layer 62 of an electrode body 60. The valve metal member 11 is arranged so as to fill the spacer 16 (refer to FIG. 1 ) of the microstructure 10. Fig.25 ), that is, the thickness of the anodic oxide film, or the resulting metal-filled microstructure 32 (reference Fig.34The size and thickness are appropriately determined according to the thickness of the sandwiching portion 16 of the valve body, the device to be processed, etc. The valve metal member 11 is, for example, a rectangular plate.

[0178] As described above, an aluminum substrate is used as the valve metal member 11 .

[0179] In addition, as the valve metal component 11, for example, an aluminum substrate can be prepared, but the valve metal component 11 can also be formed on the electrode body 60. In this case, in the valve metal layer forming step, for example, an aluminum substrate is formed on the surface 62a of the conductive layer 62 and the surface 63a of the resist layer 63 by, for example, a vapor deposition method as the valve metal component 11.

[0180] Next, an anodic oxide film forming step is performed in which an anodic oxide treatment is performed using the conductive layer 62 as an electrode, and the valve metal member 11 in the region on the conductive layer 62 of the valve metal member 11 is formed into an anodic oxide film. The anodic oxide film is an insulating base material. The first metal portion 15 is obtained by performing an anodic oxide treatment on the valve metal member 11.

[0181] In the anodic oxide film forming step, the conductive layer 62 is used as a cathode electrode and the valve metal component 11 is used as an anode electrode to perform an anodic oxidation treatment. As a result, the valve metal component 11 on the conductive layer 62 is anodized. Fig.24 As shown, an anodic oxide film 11d is formed in the region 15c of the first metal portion 15. During the anodic oxidation process, for example, if an extraction electrode is provided on the conductive layer 62, a direct current is applied to the conductive layer 62 by the extraction electrode.

[0182] In the anodizing treatment, as described above, the conductive layer 62 of the electrode body 60 is used as an electrode, and the valve metal member 11 (refer to Fig.23 ) becomes the region 11c where the anodized film 11d is formed (reference Fig.23 ), the valve metal component 11 on the resist layer 63 (reference Fig.23 ) is the outer edge 15b of the first metal portion 15, which becomes the frame portion 15d.

[0183] The anodic oxide film 11d is formed on the region 11c, but the valve metal 11 on the resist layer 63 is not anodic oxidized. Thus, the valve metal 11 is not entirely formed into the anodic oxide film 11d, and a region of the valve metal 11 remains even after the anodic oxidation process.

[0184] Thus, the frame portion 15d of the first metal portion 15 formed of the valve metal member 11 is disposed on the outer edge 15b of the first metal portion 15. The anodic oxide film 11d is formed in the region 15c surrounded by the frame portion 15d (see Fig.24 ) as the spacer 16.

[0185] In the anodizing treatment, the entire valve metal member 11 on the conductive layer 62 can be formed into the anodized film 11d. However, by adjusting the anodizing treatment time, etc., a portion of the valve metal member 11 on the conductive layer 62 can be formed into the anodized film 11d. Fig.24 In the embodiment, the first metal portion 15 exists between the conductive layer 62 and the intervening portion 16 of the anodized film.

[0186] In addition, since the valve metal member 11, that is, the first metal portion is made of aluminum, an anodic oxide film 11d is formed as an oxide film, and the anodic oxide film 11d is made of an Al2O3 film.

[0187] The anodized film 11d has a plurality of micropores when it is formed. However, among the plurality of micropores, there are also micropores that do not penetrate in the thickness direction Dt. In addition, there is a barrier layer (not shown) at the bottom of the micropores. Fig.24 The anodized film 11d shown in FIG. 1 is removed from the barrier layer. Fig.25 As shown, a plurality of through holes 17 extending in the thickness direction Dt are formed in the anodized film 11d, thereby obtaining a sandwich portion 16 constituted by the anodized film 11d.

[0188] Through the above steps, the spacer 16 (anodized film) having a plurality of pores (through holes 17) is formed in the region 15c surrounded by the frame portion 15d disposed on the outer edge 15b of the first metal portion 15, thereby obtaining a structure 18 having the first metal portion 15 and the spacer 16 (anodized film). Fig.25 As shown, a spacer 16 (anodized film) is formed on the surface 15a of the first metal part 15, and a frame part 15d exists around the spacer 16. Although not shown, the surface 16a of the spacer 16 and the upper surface of the frame part 15d are substantially flush with each other.

[0189] As mentioned above, Fig.24 The anodized film forming process shown in Fig.25 The step of forming the plurality of through holes 17 extending in the thickness direction Dt is a step of obtaining the structure 18 .

[0190] Then, if Fig.26As shown, for the structure 18, a filling process of filling the plurality of through holes 17 of the spacer 16 with metal is performed. For the structure 18, the second metal part 19 is formed by filling the plurality of through holes 17 of the spacer 16 with metal exceeding the surface 16a of the spacer 16. Thus, the filled microstructure 10 is obtained. In this case, by forming the second metal part 19, a conductive path 20 is formed. The method for forming the second metal part 19 is the same as the first example of the manufacturing method of the filled microstructure, so its detailed description is omitted.

[0191] In the filling process, metal is filled inside the plurality of through holes 17 of the sandwiching portion 16, and as shown in FIG. Fig.26 As shown in FIG. 1 , the second metal portion 19 is formed on the surface of the structure 18, that is, on the frame portion 15d of the microstructure 10 and the surface 16a of the sandwich portion 16, so that the metal is filled in the plurality of through holes 17. In this case, as described above, the thickness δ (refer to FIG. 1 ) of the portion of the second metal portion 19 existing on the frame portion 15d is Figure 2 ) is formed to be 2μm~100μm.

[0192] In addition, for example, by extending the plating time, the thickness δ of the second metal portion 19 can be increased. In the filling step, the second metal portion 19 is formed also on the frame portion 15d by filling the metal beyond the surface 16a of the spacer portion 16.

[0193] [An Example of a Method for Producing a Metal-Filled Microstructure]

[0194] A metal-filled microstructure can be obtained by subjecting the filled microstructure 10 to the following steps. A method for producing the metal-filled microstructure will be described below.

[0195] Figure 27 to Figure 34 1 is a schematic cross-sectional view showing an example of a metal-filled microstructure according to an embodiment of the present invention in order of process steps. Figure 27 to Figure 34 In, with Figures 1 to 11 The same components as shown are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0196] For example, the metal-filled microstructure is manufactured after being transported in a state of being filled with the microstructure 10. The transport of the filled microstructure 10 will be described later.

[0197] In the method for manufacturing a metal-filled microstructure, Fig. 27 As shown, relative to the filling microstructure 10 (reference Figure 2 ), a resin substrate 22 is used, and a support body 24 is provided on the back side 16b of the partition portion 16.

[0198] For example, a functional adsorption film is used as the resin substrate 22. As the functional adsorption film, Q-chuck (registered trademark) (manufactured by MARUISHI SANGYO CO., LTD.) or the like can be used.

[0199] The support body 24 preferably has the same outer shape as the sandwiching portion 16. The support body 24 supports the sandwiching portion 16 in the subsequent process. By installing the support body 24, the workability is improved.

[0200] Then, if Fig.28 As shown, a metal layer removal step is performed on the filled microstructure 10 to remove, for example, the second metal portion 19 of the filled microstructure 10. In the metal layer removal step, for example, an adhesive tape is used to peel off the second metal portion 19. The average diameter of the plurality of through holes 17 is as small as 1 μm or less, and the second metal portion can be easily removed using an adhesive tape.

[0201] In addition, the method of the metal layer removal step is not particularly limited as long as the second metal portion 19 can be removed.

[0202] Preferably with Fig.28 The surface 16a of the spacer 16 is smoothed in the state where the second metal portion 19 is removed. The surface smoothing process can be smoothed by chemical mechanical polishing (CMP), dry etching or grinding, and can also be smoothed by combining chemical mechanical polishing (CMP), dry etching and grinding. When performing chemical mechanical polishing (CMP), different abrasive grains can be combined for polishing. In any method, the surface roughness (arithmetic mean roughness Ra (JIS B 0601: 2001)) of the finished surface is preferably set to 0.02 μm or less.

[0203] By performing the surface smoothing process after the metal layer removal process, the amount of polishing in the surface smoothing process can be reduced, and polishing can be easily performed. Thus, the time required for the surface smoothing process can be shortened, and smoothing can be easily performed.

[0204] The metal layer removal step and the surface smoothing step are performed after the conveying step. In the metal layer removal step and the surface smoothing step, a support member is provided on the back surface of the first metal portion 15 for the purpose of conveying and other processes.

[0205] After the surface smoothing process, Fig.29As shown in the figure, a part of the sandwiching part 16 and the frame part 15d is removed in the thickness direction Dt so that the metal filled in the sandwiching part 16 protrudes further than the surface 16a of the sandwiching part 16 in such a manner that the support body 24 is mounted. That is, the conducting path 20 can protrude from the surface 16a of the sandwiching part 16. The part of the conducting path 20 protruding from the surface 16a of the sandwiching part 16 is referred to as a protruding part 20a. The process of making the metal filled in the sandwiching part 16 protrude further from the surface 16a of the sandwiching part 16 is referred to as a metal protruding process.

[0206] 〔Metal protrusion process〕

[0207] For the removal of the above-mentioned part of the intervening portion 16, for example, an acidic aqueous solution or alkaline aqueous solution that does not dissolve the metal constituting the conductive path 20 but dissolves the intervening portion 16, that is, aluminum oxide (Al2O3), can be used. A part of the intervening portion 16 is removed by bringing the above-mentioned acidic aqueous solution or alkaline aqueous solution into contact with the intervening portion 16 having the through hole 17 filled with metal. There is no particular limitation on the method of bringing the above-mentioned acidic aqueous solution or alkaline aqueous solution into contact with the intervening portion 16, and examples thereof include immersion method, spray method, and rotation treatment method. Among them, from the viewpoint of uniformity, a treatment method using a rotation processor is preferably used. As a rotation processor, well-known products of MIMASU SEMICONDUCTOR INDUSTRY CO., LTD., Hitachi High-Tech Corporation, SCREEN Holdings Co., Ltd., DAINIPPON SCREEN MFG.CO., LTD., Actes Kyosan inc., Kanamex Co., Ltd., etc. can be used.

[0208] When an acidic aqueous solution is used, an aqueous solution of an inorganic acid such as sulfuric acid, phosphoric acid, nitric acid, and hydrochloric acid, or a mixture thereof is preferably used. Among them, an aqueous solution not containing chromic acid is preferred from the viewpoint of excellent safety. The concentration of the acidic aqueous solution is preferably 1 to 10% by mass. The temperature of the acidic aqueous solution is preferably 25 to 60°C.

[0209] When using an alkaline aqueous solution, it is preferred to use an aqueous solution of at least one alkali selected from sodium hydroxide, potassium hydroxide, and lithium hydroxide. The concentration of the alkaline aqueous solution is preferably 0.1 to 5% by mass. The temperature of the alkaline aqueous solution is preferably 20 to 35°C.

[0210] Specifically, for example, a 50 g / L, 40° C. phosphoric acid aqueous solution, a 0.5 g / L, 30° C. sodium hydroxide aqueous solution, or a 0.5 g / L, 30° C. potassium hydroxide aqueous solution is preferably used.

[0211] The immersion time in the acidic aqueous solution or alkaline aqueous solution is preferably 8 to 120 minutes, more preferably 10 to 90 minutes, and still more preferably 15 to 60 minutes. Here, the immersion time refers to the sum of the immersion times when the immersion treatments are repeated for a short time. In addition, between the immersion treatments, a cleaning treatment may be performed, and a neutralization treatment may also be performed.

[0212] Furthermore, when the manufactured metal-filled fine structure 32 is used as an anisotropic conductive member, the metal is preferably protruded from the surface 16a of the spacer 16 by 10 nm to 1000 nm, more preferably by 50 nm to 500 nm, from the reason that the pressure-bonding property with the adherend such as a wiring substrate becomes good when the metal-filled fine structure 32 is used as an anisotropic conductive member. That is, the protrusion amount of the protrusion 20a from the surface 16a is preferably 10 nm to 1000 nm, more preferably 50 nm to 500 nm.

[0213] When the height of the protruding portion 20 a of the conducting path 20 is strictly controlled, it is preferred that after the through hole 17 is filled with metal, the spacer 16 and the end of the conducting path 20 are processed to be flush with each other, and then the anodic oxide film is selectively removed.

[0214] Furthermore, after the metal filling or after the metal protrusion step, a heat treatment may be performed for the purpose of alleviating deformation in the conducting path 20 caused by the metal filling.

[0215] From the viewpoint of suppressing metal oxidation, the heat treatment is preferably performed in a reducing atmosphere, specifically, preferably at an oxygen concentration of 20 Pa or less, and more preferably in a vacuum. Here, vacuum refers to a spatial state in which at least one of gas density and gas pressure is lower than atmospheric pressure.

[0216] Furthermore, for the purpose of correction, it is preferable to perform the heat treatment while applying stress to the intervening portion 16 .

[0217] In order to suppress the convergence of the protrusions due to the surface tension of water during drying, supercritical drying is preferably performed. For supercritical drying, for example, a supercritical cleaning drying apparatus (SCRD6, manufactured by Rexxam Co., Ltd.) or the like can be used.

[0218] By providing the support body 24 in the spacer 16 , damage to the spacer 16 can be suppressed compared to handling the spacer 16 alone, and the handling becomes easy.

[0219] Here, the term "operation" refers to holding the spacer 16 and moving the spacer 16 such as transferring, conveying, and transporting the spacer 16. "Easy to operate" means that damage to the spacer 16 can be suppressed when holding the spacer 16 and when moving the spacer 16. Due to the ease of operation, for example, the metal filled in the spacer 16 protrudes further than the surface 16a of the spacer 16, but damage to the metal can be suppressed.

[0220] like Fig.29 As shown in FIG. 1 , since the filled metal protrudes further than the surface 16a of the sandwiching portion 16, it is preferred to protect the protruding metal, that is, the protruding portion 20a of the conductive path 20. Fig.30 As shown, a resin layer 26 for embedding the protrusion 20a of the conducting path 20 is preferably formed on the surface 16a of the intervening portion 16. The step of providing the resin layer 26 is referred to as a resin layer forming step. The method for manufacturing the metal-filled microstructure 32 may include a resin layer forming step.

[0221] The resin layer 26 protects the protruding portion 20a of the conductive path 20, and can further improve the transportability of the metal-filled microstructure, making the handling easier. The resin layer 26 has adhesiveness and imparts adhesion.

[0222] The resin layer 26 can be formed using, for example, a conventionally known surface protection tape sticking device and a laminator. By providing the resin layer 26, the transportability of the metal-filled microstructure can be improved.

[0223] [Resin layer forming step]

[0224] Specifically, the resin material constituting the resin layer 26 includes, for example, ethylene copolymers, polyamide resins, polyester resins, polyurethane resins, polyolefin resins, acrylic resins and cellulose resins, but from the viewpoint of transportability and ease of use as an anisotropic conductive component, the resin layer is preferably a peelable film with an adhesive layer, and more preferably a peelable film with an adhesive layer whose adhesiveness is weakened by heat treatment or ultraviolet exposure treatment.

[0225] The film with the adhesive layer is not particularly limited, and examples thereof include a heat-peelable resin layer and an ultraviolet (UV)-peelable resin layer.

[0226] Here, the heat-peelable resin layer has adhesive strength at room temperature and can be easily peeled off only by heating, and therefore, expandable microcapsules and the like are mainly used.

[0227] Specific examples of the adhesive constituting the adhesive layer include rubber adhesives, acrylic adhesives, vinyl alkyl ether adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, and styrene-diene block copolymer adhesives.

[0228] Furthermore, the UV peelable resin layer has a UV curable adhesive layer, and loses its adhesive force by curing, thereby becoming peelable.

[0229] Examples of the UV curable adhesive layer include polymers having carbon-carbon double bonds introduced into the polymer side chains, main chains, or main chain terminals in the base polymer. As the base polymer having carbon-carbon double bonds, an acrylic polymer is preferably used as the basic skeleton.

[0230] Furthermore, the acrylic polymer may contain a polyfunctional monomer or the like as a copolymerizable monomer component, if necessary, for crosslinking.

[0231] The base polymer having a carbon-carbon double bond can be used alone, or a UV curable monomer or oligomer can be blended therein.

[0232] Regarding the UV-curable adhesive layer, in order to cure by UV irradiation, it is preferred to use a photopolymerization initiator at the same time. Examples of the photopolymerization initiator include benzoin ether compounds; ketal compounds; aromatic sulfonyl chloride compounds; photosensitive oxime compounds; benzophenone compounds; thioxanthone compounds; camphorquinone; halogenated ketones; acylphosphine oxides; acylphosphonates, etc.

[0233] Examples of commercially available products of the heat-peelable resin layer include WS5130C02, WS5130C10, and other Intellimer (registered trademark) tapes (NITTA Corporation); Somatac (registered trademark) TE series (manufactured by SOMAR Corporation); No.3198, No.3198LS, No.3198M, No.3198MS, No.3198H, No.3195, No.3196, No.3195M, No.3195MS, No.3195H, No.3195HS, No.3195V, No.3195VS, No.319Y-4L, No.319Y-4LS, No.319Y-4M, No.319Y-4MS, No.319Y-4H, No.319Y-4HS, No.319Y-4LSC, No.31935MS, No.31935HS, No.3193M, No.3193MS, etc. Riva Alpha (registered trademark) series (NITTO DENKOCORPORATION.manufactured); etc.

[0234] Commercially available products of UV peeling resin layers include ELEPH HOLDER [registered trademark] (manufactured by NITTO DENKO CORPORATION), such as ELP DU-300, ELP DU-2385KS, ELP DU-2187G, ELP NBD-3190K, and ELP UE-2091J; Adwill D-210, Adwill D-203, Adwill D-202, Adwill D-175, and Adwill D-675 (all manufactured by Lintec Corporation); SUMILITE [registered trademark] FLS N8000 series (manufactured by Sumitomo Bakelite Co., Ltd.); UC353EP-110 (manufactured by FURUKAWA ELECTRIC CO., LTD.); and other cutting tapes. In addition, as commercially available products of the UV peeling resin layer, for example, ELP RF-7232DB, ELP UB-5133D (both manufactured by NITTO DENKO CORPORATION); SP-575B-150, SP-541B-205, SP-537T-160, SP-537T-230 (all manufactured by FURUKAWA ELECTRIC CO., LTD.); and other back grinding belts can be used.

[0235] The film with an adhesive layer can be attached using a known surface protection tape attaching device and a laminator.

[0236] As a method for forming the resin layer 26, in addition to the above-mentioned method, for example, a method in which a resin composition containing an antioxidant material, a polymer material, a solvent (such as methyl ethyl ketone, etc.) described later is applied to the surface, the back side and the protruding portion of the conductive path of the partition 16, and the resulting mixture is dried and calcined as needed is cited.

[0237] The coating method of the resin composition is not particularly limited, and examples thereof include conventionally known coating methods such as gravure coating, reverse coating, die coating, doctor blade coating, roll coating, air knife coating, screen coating, rod coating, and curtain coating.

[0238] The drying method after coating is not particularly limited, and examples thereof include heating at 0°C to 100°C for several seconds to several tens of minutes in the atmosphere, and heating at 0°C to 80°C for several tens of minutes to several hours under reduced pressure.

[0239] In addition, the calcination method after drying varies depending on the polymer material used and is not particularly limited. However, when a polyimide resin is used, for example, a treatment of heating at a temperature of 160°C to 240°C for 2 minutes to 60 minutes can be mentioned, and when an epoxy resin is used, for example, a treatment of heating at a temperature of 30°C to 80°C for 2 minutes to 60 minutes can be mentioned.

[0240] Next, Fig.30 The support body 24 shown is removed from the sandwiching portion 16. In this case, the support body 24 is removed from the sandwiching portion 16 starting from the resin base material 22.

[0241] Then, if Fig.31 As shown, a release layer 27 is stacked on the surface 26a of the resin layer 26. The release layer 27 is a layer formed by stacking a support layer 28 and a release agent 29. The release agent 29 is in contact with the resin layer 26. For example, by heating to a predetermined temperature, the adhesive force of the release agent 29 is weakened, and the release layer 27 can be removed.

[0242] As the release agent 29 , for example, REVALPH A (registered trademark) manufactured by NITTO DENKO CORPORATION, SOMATAC (registered trademark) manufactured by SOMAR Corporation, or the like can be used.

[0243] Next, a support member 31 is attached to the release layer 27 using a double-sided adhesive 30. The support member 31 is disposed so as to face the support layer 28. The support member 31 has the same outer shape as the sandwiching portion 16. The support member 31 serves as a support body in subsequent steps. By attaching the support member 31, the operability is improved.

[0244] The structure of the double-sided adhesive 30 is not particularly limited as long as it can bond the support layer 28 of the release layer 27 and the support member 31 , and for example, double-sided REVALPHA (registered trademark) manufactured by NITTO DENKO CORPORATION can be used.

[0245] The support member 31 supports the sandwiching portion 16 and is composed of, for example, a silicon substrate. As the support member 31, in addition to the silicon substrate, for example, a ceramic substrate such as SiC, SiN, GaN, and alumina (Al2O3), a glass substrate, a fiber-reinforced plastic substrate, and a metal substrate can be used. The fiber-reinforced plastic substrate also includes a FR-4 (Flame Retardant Type 4) substrate as a printed circuit board.

[0246] Next, the back surface 16b of the spacer 16 is polished. In the polishing of the back surface 16b of the spacer 16, the back surface 16b of the spacer 16 and the end surface (not shown) of the guide path 20 are flattened to be flush with each other. The polishing of the back surface 16b of the spacer 16 is similar to the polishing of the back surface 16b of the spacer 16. Fig.28 The surface smoothing process performed on the surface 16a of the illustrated intervening portion 16 is the same, and therefore a detailed description thereof is omitted.

[0247] As described above, after the surface 16a of the partition portion 16 having multiple conductive paths 20 is subjected to the surface smoothing treatment process, the back surface 16b of the partition portion 16 having multiple conductive paths 20 is subjected to the surface smoothing treatment process, but the above-mentioned surface smoothing treatment process only needs to be subjected to the above-mentioned surface smoothing treatment process on at least one surface.

[0248] For example, the reflectance of each of the front surface 16a and the back surface 16b of the spacer 16 is measured using a sensor (not shown). If the reflectance value is within a preset range, polishing is not performed and the process can be transferred to the next step.

[0249] Then, if Fig.32 As shown in the figure, a part of the spacer 16 and the frame part 15d is removed in the thickness direction Dt, so that the metal filled above is made to protrude further than the back surface 16b of the spacer 16. That is, the conductive path 20 is made to protrude from the back surface 16b of the spacer 16. The part of the conductive path 20 protruding from the back surface 16b of the spacer 16 is referred to as the protruding part 20b.

[0250] The process of making the filled metal protrude further than the back surface 16 b of the spacer 16 is the same as the above-mentioned metal protruding process, and thus a detailed description thereof is omitted.

[0251] Then, if Fig.33 As shown in FIG. 1 , a resin layer 26 is formed on the back surface 16b of the sandwiching portion 16 to bury the protruding portion 20b of the conductive path 20 on the back surface 16b of the sandwiching portion 16. Thus, a Fig.33 The metal-filled microstructure 32 is shown.

[0252] In addition, the method of forming the resin layer 26 in which the protruding portion 20 b of the conducting path 20 is embedded is the same as the above-mentioned resin layer forming step, and thus the detailed description thereof is omitted.

[0253] like Fig.33 As shown in FIG. 1 , in a state where the resin layer 26 is formed on both sides of the sandwiching portion 16, the frame portion 15d remains at the outer edge of the sandwiching portion 16. The frame portion 15d remaining at the outer edge can be removed by a physical method such as dissolution or grinding. Fig.34As shown, a metal-filled microstructure 32 consisting of a single body of the sandwiching portion 16 can be obtained. In addition, if the first metal portion 15 can be removed without damaging the sandwiching portion 16, etc., it is not limited to dissolution. Removing the first metal portion 15 such as the aluminum substrate is referred to as the first metal portion removal process. The first metal portion removal process will be described later.

[0254] If the metal-filled microstructure 32 is in the shape of a disk, for example, the metal-filled microstructure 32 can be transported using a device used for transporting semiconductor wafers, and handling of the metal-filled microstructure 32 does not require a special device.

[0255] [1st metal part removal process]

[0256] For example, in the treatment liquid for dissolving the first metal part composed of the valve metal component, when the first metal part is an aluminum substrate, the aluminum substrate is preferably dissolved using a treatment liquid that is difficult to dissolve the spacer 16 that is an anodized film of aluminum and easy to dissolve aluminum. The dissolution rate of aluminum is preferably 1 μm / minute or more, more preferably 3 μm / minute or more, and further preferably 5 μm / minute or more. Similarly, the dissolution rate of the anodized film is preferably 0.1 nm / minute or less, more preferably 0.05 nm / minute or less, and further preferably 0.01 nm / minute or less.

[0257] Specifically, the treatment liquid preferably contains at least one metal compound having a lower ionization tendency than aluminum and has a pH (hydrogen ion index) of 4 or less or 8 or more. The pH is more preferably 3 or less or 9 or more, and even more preferably 2 or less or 10 or more.

[0258] As such a treatment liquid, a treatment liquid preferably is based on an acid or alkaline aqueous solution, for example, a treatment liquid prepared by mixing compounds of manganese, zinc, chromium, iron, cadmium, cobalt, nickel, tin, lead, antimony, bismuth, copper, mercury, silver, palladium, platinum, gold (such as chloroplatinic acid), their fluorides, their chlorides, etc.

[0259] Among them, an acidic aqueous solution base is preferred, and a mixed chloride is preferred.

[0260] In particular, from the viewpoint of the treatment range, a treatment liquid in which mercuric chloride is mixed in a hydrochloric acid aqueous solution (hydrochloric acid / mercuric chloride) or a treatment liquid in which cupric chloride is mixed in a hydrochloric acid aqueous solution (hydrochloric acid / cupric chloride) is preferred.

[0261] The composition of the treatment liquid is not particularly limited, and for example, a bromine / methanol mixture, a bromine / ethanol mixture, aqua regia, etc. can be used.

[0262] Furthermore, the acid or alkali concentration of the treatment liquid is preferably 0.01 to 10 mol / L, more preferably 0.05 to 5 mol / L.

[0263] The treatment temperature using such a treatment liquid is preferably -10°C to 80°C, more preferably 0°C to 60°C.

[0264] Furthermore, the dissolution of the first metal portion 15 is carried out by bringing the first metal portion 15 into contact with the treatment liquid after the metal layer removal step. The contact method is not particularly limited, and examples thereof include an immersion method and a spray method. Among them, an immersion method is preferred. The contact time at this time is preferably 10 seconds to 5 hours, and more preferably 1 minute to 3 hours.

[0265] An example of the structure of the metal-filled microstructure will be described below.

[0266] [An example of the structure of a metal-filled microstructure]

[0267] Fig.35 is a plan view showing an example of the structure of a metal-filled microstructure according to an embodiment of the present invention, Fig.36 This is a schematic cross-sectional view showing an example of the structure of the metal-filled microstructure according to the embodiment of the present invention. Fig.36 yes Fig.35 Section view of section line IB-IB.

[0268] As mentioned above, Fig.35 and Fig.36 The metal-filled microstructure 32 shown has a spacer 16 as an insulating substrate, a through hole 17 penetrating along the thickness direction Dt of the spacer 16, and a plurality of conductive paths 20 composed of metal filled in the through hole 17. As described above, the spacer 16 is composed of, for example, an anodic oxide film. The plurality of conductive paths 20 are provided in a state of being electrically insulated from each other. In addition, for example, a resin layer 26 is provided on the surface 16a and the back surface 16b of the spacer 16.

[0269] Here, “a state in which the conduction paths 20 existing inside the intervening portion 16 are electrically insulated from each other” means a state in which the conduction paths 20 existing inside the intervening portion 16 have sufficiently low conductivity to each other inside the intervening portion 16 .

[0270] The metal-filled fine structure 32 is a member that electrically insulates the conduction paths 20 from each other, has sufficiently low conductivity in the direction x orthogonal to the thickness direction Dt of the intervening portion 16, has conductivity in the thickness direction Dt, and exhibits anisotropic conductivity. The metal-filled fine structure 32 is arranged so that the thickness direction Dt coincides with, for example, the stacking direction of the electronic element described later.

[0271] like Fig.35 and Fig.36 As shown, the conducting paths 20 are provided so as to penetrate the intervening portion 16 in the thickness direction Dt in a state where they are electrically insulated from each other.

[0272] The thickness h of the metal-filled microstructure 32 is, for example, 40 μm or less. Furthermore, the TTV (Total Thickness Variation) of the metal-filled microstructure 32 is preferably 10 μm or less. Since the surface 16 a and the back surface 16 b of the spacer 16 are ground, the thickness is thicker than the thickness h of the metal-filled microstructure 32, for example, more than 60 μm, but is preferably about 40 μm from the viewpoint of brittleness.

[0273] Here, the thickness h of the metal-filled microstructure 32 and the thickness of the sandwich portion 16 are obtained by cutting the metal-filled microstructure 32 and the sandwich portion 16 in the thickness direction using a focused ion beam (FIB), observing their cross-sections with a field emission scanning electron microscope at a magnification of 200,000 times to obtain the contour shapes of the metal-filled microstructure 32 and the sandwich portion 16, and measuring the average value of 10 points in the area equivalent to the thickness h.

[0274] The TTV (Total Thickness Variation) of the metal-filled microstructure 32 is a value obtained by cutting the metal-filled microstructure 32 together with the support member 31 by dicing and observing the cross-sectional shape of the metal-filled microstructure 32 .

[0275] The metal-filled fine structure 32 can be used as an anisotropic conductive component showing anisotropic conductivity, for example. In this case, semiconductor elements and semiconductor elements are joined via the metal-filled fine structure 32, and an electronic element in which the semiconductor elements and semiconductor elements are electrically connected can be obtained. In the electronic element, the metal-filled fine structure 32 plays the role of TSV (Through Silicon Via: silicon through hole).

[0276] In addition, it is also possible to use an electronic component in which three or more semiconductor elements are electrically connected using the metal-filled fine structure 32. By using the metal-filled fine structure 32, three-dimensional mounting can be performed.

[0277] The number of semiconductor elements to be bonded is not particularly limited and is appropriately determined according to the function of the electronic element and the performance required of the electronic element.

[0278] Thermocompression bonding can be used for bonding with electronic components. If bonding is performed in a reducing atmosphere, the metal electrode and the protrusion can be easily bonded at a temperature of 250° C. or less, thereby reducing the thermal influence on the device.

[0279] By using the metal-filled microstructure 32, the size of the electronic component can be reduced and the mounting area can be reduced. In addition, by reducing the thickness of the metal-filled microstructure 32, the wiring length between the semiconductor components can be shortened, signal delay can be suppressed, and the processing speed of the electronic component can be increased. By shortening the wiring length between the semiconductor components, power consumption can also be suppressed.

[0280] As described above, the metal-filled microstructure 32 has high shape accuracy because the spacer 16 and the conducting path 20 are polished so as to be flush with the surface 16a of the spacer 16.

[0281] Furthermore, as described above, the height of the protruding portion 20 a of the conductive path 20 can be strictly controlled, so that the reliability of the electrical connection between semiconductor elements is excellent.

[0282] Furthermore, since the metal-filled microstructure 32 is densely filled with metal, its thermal conductivity is higher than that of resin materials. The thermal conductivity in the vertical direction between the connected electrodes and between the semiconductor elements and the thermal diffusion in the plane direction are large, so it is particularly useful for components that need to dissipate heat. In addition to the above-mentioned semiconductor elements, the metal-filled microstructure 32 can also be used for heat dissipation of metal base substrates, etc., and is also effective for connecting heat sinks. In addition, it is very effective for the connection of memories, etc., where heat generation caused by multi-layer connections becomes a problem.

[0283] As semiconductor elements, for example, logic integrated circuits such as ASIC (Application Specific Integrated Circuit), FPGA (Field Programmable Gate Array), and ASSP (Application Specific Standard Product) can be cited. Also, for example, microprocessors such as CPU (Central Processing Unit) and GPU (Graphics Processing Unit) can be cited. Also, for example, memories such as DRAM (Dynamic Random Access Memory), HMC (Hybrid Memory Cube), MRAM (Magneto resistive Random Access Memory), PCM (Phase-Change Memory), ReRAM (Resistance Random Access Memory), FeRAM (Ferroelectric Random Access Memory), and flash memory can be cited. In addition, examples include analog integrated circuits such as LEDs (Light Emitting Diodes), power devices, DC (Direct Current)-DC (Direct Current) converters, and insulated gate bipolar transistors (IGBTs). In addition, examples include MEMS (Micro Electro Mechanical Systems) such as acceleration sensors, pressure sensors, vibrators, and gyro sensors.In addition, for example, wireless components such as GPS (Global Positioning System), FM (Frequency Modulation), NFC (Nearfield communication), RFEM (RF Expansion Module), MMIC (Monolithic Microwave Integrated Circuit), WLAN (Wireless Local Area Network), discrete components, CMOS (Complementary Metal Oxide Semiconductor), CMOS image sensors, camera modules, passive devices, SAW (Surface Acoustic Wave) filters, RF (Radio Frequency) filters, IPD (Integrated Passive Devices), etc. can be cited.

[0284] Furthermore, the semiconductor element may have an element region, which is an area where various elements constituting circuits for functioning as electronic elements are formed. In the element region, for example, there are the following areas: areas where memory circuits such as flash memory, logic circuits such as microprocessors and FPGAs (field-programmable gate arrays), and areas where communication modules and wiring such as wireless tags are formed. In addition, MEMS (Micro Electro Mechanical Systems) may be formed in the element region. MEMS are, for example, sensors, actuators, and antennas. Among the sensors, for example, various sensors such as acceleration sensors, sound sensors, and optical sensors are included. As long as the optical sensor can detect light, it is not particularly limited. For example, a CCD (Charge Coupled Device) image sensor or a CMOS (Complementary Metal Oxide Semiconductor) image sensor may be used.

[0285] The semiconductor element is appropriately selected according to the function to be realized in the electronic element. For example, in the electronic element, a semiconductor element having a logic circuit and a semiconductor element having a memory circuit can be combined. In addition, as a combination of semiconductor elements in the electronic element, a sensor, an actuator, an antenna, etc., a memory circuit and a logic circuit can be combined.

[0286] The semiconductor element is made of, for example, silicon, but is not limited thereto, and may be made of silicon carbide, germanium, gallium arsenide, gallium nitride, or the like.

[0287] Furthermore, in addition to the semiconductor element, two wiring layers can be electrically connected using the metal-filled fine structure 32 .

[0288] Hereinafter, the structures of the filled microstructure and the metal-filled microstructure will be described in more detail.

[0289] 〔1st Metal Division〕

[0290] The first metal portion 15 (reference Figure 2 ) constitutes a filled microstructure 10 (reference Figure 2 ), as described above, at the outer edge 15b (reference Figure 2 ) has a frame portion 15d (reference Figure 2 ). The first metal portion 15 includes a metal selected from valve metals. For example, as described above, the valve metal component 11 (refer to Figure 1 ), an aluminum substrate is used as the valve metal component 11. The aluminum substrate is as described above.

[0291] Here, specific examples of the valve metal contained in the first metal portion 15 include tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, and the like, in addition to the above-mentioned aluminum.

[0292] The first metal portion 15 contains a metal selected from valve metals, which means that the content is 99 mass % or more.

[0293] 〔Metal Division 2〕

[0294] The second metal portion 19 (reference Figure 2 ) constitutes the filled microstructure 10, as described above, the plurality of through holes 17 (reference Figure 2 ), and is in direct contact with the frame portion 15d of the first metal portion 15, and the thickness δ on the frame portion 15d (reference Figure 2 ) is 2 μm or more. The second metal portion 19 functions as a protective film for the through-holes 17 of the spacer portion 16 and the frame portion.

[0295] The portion of the second metal portion 19 that is filled in the plurality of through holes 17 of the intervening portion 16 constitutes a metal-filled fine structure 32 (see Fig.36 ) of the conducting path 20 (reference Fig.36 ) Therefore, as the second metal portion 19, a metal constituting a conductive path described later is used, for example, copper.

[0296] 〔Partition〕

[0297] As described above, the spacer 16 has a plurality of pores (through holes), and the average diameter of the plurality of pores (through holes) is 1 μm or less. As described above, the spacer 16 contains an oxide of a metal selected from valve metals and contained in the first metal part. That is, the spacer 16 contains an oxide of the valve metal constituting the first metal part. For example, if the first metal part 15 is composed of an aluminum substrate, the spacer 16 is composed of an aluminum polar oxide film.

[0298] The spacer 16 constitutes the metal-filled microstructure 32 (refer to Fig.36 ), forming an insulating substrate in the metal-filled microstructure. The spacing between each conductive path in the sandwiching part 16 is preferably 5nm to 800nm, more preferably 10nm to 200nm, and further preferably 20nm to 60nm. If the spacing between each conductive path in the sandwiching part 16 is within this range, the sandwiching part 16 fully functions as an insulating partition.

[0299] Here, the interval between each conductive path refers to the width w between adjacent conductive paths and is the average value of the widths between adjacent conductive paths measured at 10 points by observing a cross section of the metal-filled microstructure 32 at a magnification of 200,000 using a field emission scanning electron microscope.

[0300] <Average pore diameter>

[0301] The average diameter of the pores, that is, the average diameter d of the through-holes 17 (refer to Fig.35 , Fig.36 ) is 1 μm or less, preferably 5 to 500 nm, more preferably 20 to 400 nm, further preferably 40 to 200 nm, and most preferably 50 to 100 nm. If the average diameter d of the through hole 17 is 1 μm or less, within the above range, a sufficient response can be obtained when an electrical signal flows through the resulting conductive path 20, so it can be more preferably used as a connector for testing electronic components. In addition, if the average diameter d of the through hole 17 is 1 μm or less, the second metal portion 19 (reference Fig.26 ).

[0302] Regarding the average diameter d of the through hole 17, a photographic image is obtained by using a scanning electron microscope to photograph the surface of the partition portion 16 from directly above at a magnification of 100 to 10,000 times. At least 20 through holes connected in a ring shape are extracted from the photographic image, and their diameters are measured and set as the opening diameter. The average value of these opening diameters is calculated as the average diameter of the through holes.

[0303] In addition, the magnification can be appropriately selected within the above range to obtain a photographic image capable of extracting more than 20 through-holes. In addition, regarding the opening diameter, the maximum value of the distance between the ends of the through-hole portion is measured. That is, since the shape of the opening portion of the through-hole is not limited to a substantially circular shape, when the shape of the opening portion is non-circular, the maximum value of the distance between the ends of the through-hole portion is set as the opening diameter. Therefore, in the case of a through-hole having a shape such as two or more through-holes integrated, it is also regarded as one through-hole, and the maximum value of the distance between the ends of the through-hole portion is set as the opening diameter.

[0304] 〔Conduction Path〕

[0305] As described above, the plurality of conducting paths 20 are provided in a columnar shape so as to penetrate in the thickness direction Dt of the sandwiching part 16 and be electrically insulated from each other. The conducting paths 20 are made of metal. The conducting paths 20 may have protrusions protruding from the front and back surfaces of the sandwiching part 16, and the protrusions of each conducting path are buried in the resin layer.

[0306] Specific examples of the metal constituting the conductive path preferably include gold (Au), silver (Ag), copper (Cu), aluminum (Al), magnesium (Mg), and nickel (Ni). From the viewpoint of conductivity, copper, gold, aluminum, and nickel are preferred, and copper and gold are more preferred.

[0307] <Protrusion>

[0308] The protruding portions 20 a and 20 b of the conducting path 20 are portions of the conducting path 20 protruding from the front surface 16 a and the back surface 16 b of the intervening portion 16 , and are preferably protected by the resin layer 26 .

[0309] When the metal-filled microstructure 32 is used as an anisotropic conductive component, when the anisotropic conductive component is electrically connected or physically joined to an electrode by crimping or the like, the aspect ratio of the protrusion of the conductive path (height of the protrusion / diameter of the protrusion) is preferably greater than 0.5 and less than 50, more preferably 0.8 to 20, and even more preferably 1 to 10, for the reason that the insulation in the surface direction when the protrusion is flattened can be sufficiently ensured.

[0310] Furthermore, from the viewpoint of following the surface shape of the semiconductor element or semiconductor wafer to be connected, the height of the protruding portion of the conductive path is preferably 20 nm or more, and more preferably 100 nm to 500 nm.

[0311] The height of the protruding portion of the conducting path is the average value of the height of the protruding portion of the conducting path measured at 10 points by observing a cross section of the anisotropic conductive member at a magnification of 20,000 times using a field emission scanning electron microscope.

[0312] The diameter of the protruding portion of the conducting path is the average value of the diameters of the protruding portion of the conducting path measured at 10 points by observing a cross section of the anisotropic conductive member with a field emission scanning electron microscope.

[0313] <Other shapes>

[0314] The density of the conductive paths 20 is preferably 20,000 per mm. 2 More than 2 million / mm 2 More than 10 million pieces / mm 2 More than 50 million / mm is particularly preferred 2 More than 100 million pieces / mm is most preferred 2 above.

[0315] In addition, the center distance p between adjacent conductive paths 20 (refer to Fig.35 and Fig.36 ) is preferably 20 nm to 500 nm, more preferably 40 nm to 200 nm, and further preferably 50 nm to 140 nm.

[0316] 〔Resin layer〕

[0317] As described above, the resin layer 26 is provided on the front surface 16a and the back surface 16b of the intervening portion 16, and as described above, the protruding portions 20a and 20b of the conducting path 20 are buried. That is, the resin layer 26 covers the end portions of the conducting path 20 protruding from the intervening portion 16 and protects the protruding portions 20a and 20b.

[0318] The resin layer 26 is formed by the above-mentioned resin layer forming step. The resin layer 26 imparts adhesiveness to the connection object. The resin layer 26 is preferably a resin layer that exhibits fluidity in a temperature range of 50°C to 200°C and cures at a temperature of 200°C or higher.

[0319] The resin layer 26 is formed by the above-mentioned resin layer forming step, but the composition of the resin layer shown below can also be used. The composition of the resin layer is described below. For example, the resin layer contains a polymer material and may also contain an antioxidant material.

[0320] <Polymer Materials>

[0321] The polymer material contained in the resin layer is not particularly limited, but is preferably a thermosetting resin because it can efficiently fill the gap between the semiconductor element or semiconductor wafer and the anisotropic conductive component and further improve the adhesion with the semiconductor element or semiconductor wafer.

[0322] Specific examples of the thermosetting resin include epoxy resins, phenol resins, polyimide resins, polyester resins, polyurethane resins, bismaleimide resins, melamine resins, and isocyanate resins.

[0323] Among them, polyimide resin and / or epoxy resin are preferably used because of further improving insulation reliability and excellent chemical resistance.

[0324] <Antioxidant Materials>

[0325] Specific examples of the antioxidant material contained in the resin layer include 1,2,3,4-tetrazole, 5-amino-1,2,3,4-tetrazole, 5-methyl-1,2,3,4-tetrazole, 1H-tetrazole-5-acetic acid, 1H-tetrazole-5-succinic acid, 1,2,3-triazole, 4-amino-1,2,3-triazole, 4,5-diamino-1,2,3-triazole, 4-carboxyl-1H-1,2,3-triazole, 4,5-dicarboxyl-1H-1,2,3-triazole, 1H-1,2,3-triazole-4-acetic acid, 4-carboxyl-5-carboxyl Methyl-1H-1,2,3-triazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, 3,5-diamino-1,2,4-triazole, 3-carboxy-1,2,4-triazole, 3,5-dicarboxy-1,2,4-triazole, 1,2,4-triazole-3-acetic acid, 1H-benzotriazole, 1H-benzotriazole-5-carboxylic acid, benzofuran, 2,1,3-benzothiazole, o-phenylenediamine, m-phenylenediamine, catechol, o-aminophenol, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, melamine and derivatives thereof.

[0326] Among these, benzotriazole and its derivatives are preferred.

[0327] Examples of benzotriazole derivatives include substituted benzotriazoles having a hydroxyl group, an alkoxy group (e.g., a methoxy group, an ethoxy group, etc.), an amino group, a nitro group, an alkyl group (e.g., a methyl group, an ethyl group, and a butyl group), a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, etc.) on the benzene ring of the benzotriazole. Also, examples include naphthalenetriazole, naphthalenebistriazole, substituted naphthalenetriazoles substituted in the same manner, and substituted naphthalenebistriazoles.

[0328] Furthermore, other examples of the antioxidant material contained in the resin layer include higher fatty acids, higher fatty acid copper, phenol compounds, alkanolamines, hydroquinones, copper chelating agents, organic amines, and organic ammonium salts, which are common antioxidants.

[0329] The content of the antioxidant material contained in the resin layer is not particularly limited, but is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, relative to the total mass of the resin layer from the viewpoint of the anticorrosion effect. Also, from the perspective of obtaining an appropriate resistance in the actual bonding process, it is preferably 5.0% by mass or less, more preferably 2.5% by mass or less.

[0330] <Anti-migration materials>

[0331] The resin layer preferably contains a migration prevention material because the resin layer can capture metal ions, halogen ions, and metal ions derived from the semiconductor element and the semiconductor wafer that may be contained in the resin layer, thereby further improving insulation reliability.

[0332] As the migration preventing material, for example, an ion exchanger can be used, specifically, a mixture of a cation exchanger and an anion exchanger or only a cation exchanger can be used.

[0333] Here, the cation exchanger and the anion exchanger can be appropriately selected from, for example, inorganic ion exchangers and organic ion exchangers described below, respectively.

[0334] (Inorganic ion exchanger)

[0335] Examples of the inorganic ion exchanger include metal hydroxides represented by zirconium hydroxide.

[0336] As the types of metals, for example, iron, aluminum, tin, titanium, antimony, magnesium, beryllium, indium, chromium, bismuth, and the like are known in addition to zirconium.

[0337] Among them, zirconium metals have cation Cu 2+ 、Al 3+ In addition, iron metals also have Ag + , Cu 2+ Similarly, tin, titanium and antimony metals are cation exchangers.

[0338] On the other hand, bismuth metals have anions Cl - exchange capacity.

[0339] Furthermore, zirconium-based metals exhibit anion exchange capacity depending on conditions. The same is true for aluminum-based and tin-based metals.

[0340] As other inorganic ion exchangers, there are known acid salts of polyvalent metals represented by zirconium phosphate, heteropolyacid salts represented by ammonium molybdenum phosphate, and synthetic products such as insoluble ferrocyanide.

[0341] Some of these inorganic ion exchangers are commercially available, and various grades are known under the trade name "IXE" from TOAGOSEI CO., LTD., for example.

[0342] In addition to synthetic products, inorganic ion exchanger powders such as natural products such as zeolite and montmorillonite can also be used.

[0343] (Organic ion exchanger)

[0344] Examples of the organic ion exchanger include crosslinked polystyrene having a sulfonic acid group as a cation exchanger, and further examples include crosslinked polystyrene having a carboxylic acid group, a phosphonic acid group, or a phosphinic acid group.

[0345] Furthermore, cross-linked polystyrene having a quaternary ammonium group, a quaternary phosphonium group or a tertiary sulfonium group can be mentioned as an anion exchanger.

[0346] These inorganic ion exchangers and organic ion exchangers may be appropriately selected in consideration of the types of cations and anions to be captured and the exchange capacity of the ions. Of course, inorganic ion exchangers and organic ion exchangers may be mixed and used.

[0347] Since the manufacturing process of electronic components includes a heating step, an inorganic ion exchanger is preferred.

[0348] Furthermore, for example, from the viewpoint of mechanical strength, the mixing ratio of the migration prevention material to the polymer material is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 2.5% by mass or less. Furthermore, from the viewpoint of suppressing migration when bonding a semiconductor element or a semiconductor wafer to an anisotropic conductive component, the migration prevention material is preferably 0.01% by mass or more.

[0349] <Inorganic fillers>

[0350] The resin layer may contain an inorganic filler.

[0351] The inorganic filler is not particularly limited and can be appropriately selected from known inorganic fillers. For example, kaolin, barium sulfate, barium titanate, silicon oxide powder, fine powdered silicon oxide, fumed silica, amorphous silica, crystalline silica, fused silica, spherical silica, talc, clay, magnesium carbonate, calcium carbonate, aluminum oxide, aluminum hydroxide, mica, aluminum nitride, zirconium oxide, yttrium oxide, silicon carbide and silicon nitride can be mentioned.

[0352] In order to prevent the inorganic filler from entering between the conducting paths and further improve the conduction reliability, the average particle size of the inorganic filler is preferably larger than the interval between the conducting paths.

[0353] The average particle size of the inorganic filler is preferably 30 nm to 10 μm, more preferably 80 nm to 1 μm.

[0354] Here, regarding the average particle size, the primary particle size measured by a laser diffraction and scattering particle size measuring apparatus (Microtrac MT3300 manufactured by NIKKISOC O., LTD.) is defined as the average particle size.

[0355] <Curing agent>

[0356] The resin layer may contain a curing agent.

[0357] When a curing agent is contained, it is more preferable to contain a curing agent that is liquid at room temperature rather than a solid curing agent at room temperature from the viewpoint of suppressing poor bonding with the surface shape of a semiconductor element or semiconductor wafer to be connected.

[0358] Here, "solid at room temperature" means a substance that is solid at 25°C, for example, a substance having a melting point higher than 25°C.

[0359] Specific examples of the curing agent include aromatic amines such as diaminodiphenylmethane and diaminodiphenyl sulfone, aliphatic amines, imidazole derivatives such as 4-methylimidazole, dicyandiamide, tetramethylguanidine, thiourea-added amines, carboxylic anhydrides such as methylhexahydrophthalic anhydride, carboxylic acid hydrazides, carboxylic acid amides, polyphenol compounds, novolac resins, and polythiol, and a curing agent that is liquid at 25° C. can be appropriately selected from these curing agents. The curing agent may be used alone or in combination of two or more.

[0360] The resin layer may contain various additives such as a dispersant, a buffer, and a viscosity adjuster, which are generally widely added to a resin insulating film of a semiconductor package, within a range not impairing the characteristics thereof.

[0361] <Shape>

[0362] For the purpose of protecting the conductive path 20 of the metal-filled fine structure 32 , the thickness of the resin layer is larger than the height of the protruding portions 20 a and 20 b of the conductive path 20 and is preferably 1 μm to 5 μm.

[0363] As described above, the filled microstructure 10 is transported, and the transport process will be described below. The filled microstructure 10 is transported after being stacked, for example.

[0364] Transport means moving the filled microstructure 10. The movement includes movement within a facility during a processing step and movement using a moving tool such as a vehicle, railway, airplane, or ship.

[0365] [Transportation process]

[0366] Fig.37 This is a schematic perspective view showing an example of a container used in the transport step according to the embodiment of the present invention.

[0367] In the conveying step, for example, the filled microstructure 10 is stored in Fig.37 The container 40 is shown for transportation. The container 40 includes a container body 42 and a cover 44. In the container 40, an opening 42a of the container body 42 is closed by the cover 44, and the container body 42 is sealed.

[0368] Inside the container 42b, for example, a shelf (not shown) is provided. Fig.38 As shown, among the plurality of filled fine-structure bodies 10, for example, a protective layer 45 is disposed on the second metal portion 19 of the filled fine-structure body 10, and the plurality of filled fine-structure bodies 10 are stacked and disposed on a rack.

[0369] Paper, resin film, or the like can be used as the protective layer 45 . The protective layer 45 may at least cover the second metal portion 19 filling the fine-structure body 10 .

[0370] If the filled microstructures 10 are in contact and stacked, there is a possibility that the second metal portion 19 of the filled microstructure 10 may be damaged when the filled microstructures 10 rub against each other due to vibration of the filled microstructure 10, or the sandwiching portion 16 below the second metal portion 19 may be damaged. Therefore, as described above, the filled microstructure 10 is provided with a protective layer 45 on the second metal portion 19. Thus, damage to the second metal portion 19 of the filled microstructure 10 can be suppressed.

[0371] Furthermore, as described above, the filled microstructure 10 has a rectangular shape, and various containers that can accommodate rectangular substrates can be used as the container 40 .

[0372] When the filled microstructure 10 is a circular shape similar to that of a general semiconductor wafer, various containers for storing semiconductor wafers can be used as the container 40. As the container 40, a transport container for semiconductor wafers can be used, for example, a front opening wafer transfer box (FOUP) and a front opening wafer shipping box (FOSB) can be used.

[0373] like Fig.39 As shown, the container 40 can be stored in the storage bag 50. The storage bag 50 is made of, for example, a gas barrier film. The gas barrier film is, for example, a film with low water vapor permeability, and can be a known film for packaging electronic parts, or a gas barrier film for organic EL (Electro Luminescence), electronic paper, or solar cell.

[0374] The gas barrier properties are evaluated by water vapor permeability, which is measured by the MOCON method or the like.

[0375] When the container 40 is stored in the storage bag 50, the water vapor permeability of the storage bag 50 is low, and it is difficult to adjust the humidity inside from the outside, so it is preferable to set a desiccant 51 inside the storage bag 50. The amount of the desiccant 51 is calculated in advance based on the water vapor permeability of the storage bag 50 used, the size of the container 40, and the storage time, and the calculated amount of the desiccant 51 is set inside the storage bag 50. In addition, when stored in the storage bag 50, the pressure is set to a pressure lower than the atmospheric pressure, so that the filled microstructure 10 can be transported under reduced pressure.

[0376] like Fig.39 As shown, when using the storage bag 50, Fig.37 The container 40 shown is not necessary. Fig.38 As shown, for example, Fig.38 As shown, a protective layer 45 can be arranged on the second metal part 19 of the filled microstructure 10, and a plurality of filled microstructures 10 can be stacked and stored in a storage bag 50. The filled microstructures 10 can be transported in this state. When stored in the storage bag 50, in order to adjust the humidity, it is also preferable to Fig.39 As shown, a moisture absorbent 51 is disposed inside the storage bag 50 .

[0377] And, for example, Fig.38 As shown, the protective layer 45 can be disposed on the second metal portion 19 of the filled fine-structure body 10, and the filled fine-structure body 10 can be transported in a stacked state.

[0378] The present invention is basically configured as described above. Although the filling microstructure and the delivery method of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments, and various improvements or changes can be made without departing from the gist of the present invention.

[0379] (Example 1)

[0380] Below, enumerate embodiment, feature of the present invention is described in more detail.Material, reagent, amount of substance and its ratio and operation etc. shown in following example, as long as do not depart from the gist of the present invention, just can change suitably.Therefore, the scope of the present invention is not limited to following example.

[0381] In this example, filled microstructures of Examples 1 to 6 and Comparative Example 1 were produced. The uniformity and processability of the filled microstructures of Examples 1 to 6 and Comparative Example 1 were evaluated. Hereinafter, each evaluation item of uniformity and processability will be described.

[0382] The evaluation of uniformity will be described.

[0383] <Evaluation of uniformity>

[0384] For the filled microstructures, after grinding away the second metal part, the surface (ground surface) of the sandwich part is ground by 10 μm in the thickness direction using an optical microscope, and an attempt is made to find defects with a diameter of 20 μm or more in a field of view equivalent to 1 mm 2 . Then, the number of defects is counted, and the number of defects per unit area (pieces / mm 2 ) is obtained. The number of defects per unit area (pieces / mm 2 ) is evaluated according to the evaluation criteria shown below. Hereinafter, the number of defects is Nd (pieces / mm 2 ).

[0385] In addition, the above grinding was carried out as follows. First, the filled microstructures were attached by a Q-chuck (registered trademark) (manufactured by MARUISH I SANGYO CO., LTD.), and the filled microstructures were ground using a grinding device (BC-15CN (trade name)) manufactured by MAT Inc. until the arithmetic mean roughness (JIS B0601: 2001) became 0.005 μm. As the grinding, primary grinding was carried out using an abrasive containing alumina (a liquid obtained by diluting WA#8000 (FF), manufactured by Kemet Japan Co., Ltd., 4 times with pure water), and secondary grinding was carried out using an abrasive containing silica (S-A1-1-0, manufactured by Kemet Japan Co., Ltd.).

[0386] Evaluation criteria

[0387] A: Nd ≤ 0.01 pieces / mm 2

[0388] B: 0.01 < Nd ≤ 0.05 pieces / mm 2

[0389] C: 0.05 pieces / mm 2 <Nd

[0390] An explanation is given regarding the evaluation of workability.

[0391] <Evaluation of workability>

[0392] For the filled microstructures, the second metal part is ground, and the time until the surface of the sandwich part is exposed is measured as the grinding time. In addition, when there is no second metal part on the sandwich part, the grinding time when the grinding amount is 10 μm is measured.

[0393] Regarding the processability, the grinding time without the second metal part on the spacer was set to 1, and this was used as the standard grinding time. The grinding time of the filled microstructure in each example was used as the actual grinding time. The processing time expressed as standard grinding time / actual grinding time was calculated. That is, processing time = standard grinding time / actual grinding time.

[0394] The obtained processing time is evaluated according to the evaluation criteria shown below. The larger the numerical value of the processing time, the shorter the actual grinding time. Hereinafter, the processing time is referred to as Wt.

[0395] Evaluation Benchmarks

[0396] A: 1≦Wt

[0397] B: 0.8≦Wt<1

[0398] C: Wt<0.8

[0399] <Grinding process>

[0400] In the polishing process, a polishing device (BC-15CN (trade name)) manufactured by MAT Inc. is used to perform CMP (Chemical Mechanical Polishing) treatment on the surface of the anodized film (spacer). The surface is polished once with an abrasive containing aluminum oxide (WA#8000 (FF), manufactured by Kemet Japan Co., Ltd., a liquid diluted 4 times with pure water), and then polished twice with an abrasive containing silicon dioxide (S-A1-1-0, manufactured by Kemet Japan Co., Ltd.). The arithmetic mean roughness (JIS (Japanese Industrial Standard) B0601: 2001) of the finishing after polishing is set to 0.005 μm.

[0401] Hereinafter, Examples 1 to 5 and Comparative Examples 1 and 2 will be described.

[0402] (Example 1)

[0403] The filled microstructure of Example 1 will be described.

[0404] [Filling microstructures]

[0405] <Aluminum substrate>

[0406] An aluminum substrate having a purity of 99.999% by mass was used and the thickness of the aluminum substrate was set to 120 μm.

[0407] The aluminum substrate was trimmed to a size of 15 cm square, and a high-viscosity tape was attached to form a frame with a width of 5 mm around it. The size of the sandwiching portion 16 inside the frame was set to 14 cm square. For the high-viscosity tape, Dunplon (registered trademark) tape No. 375 (width 25 mm×length 50 m) manufactured by NITTO DENKO CS SYSTEM CORPORATION was used.

[0408] <Electrolytic grinding treatment>

[0409] The aluminum substrate was subjected to electrolytic polishing treatment using an electrolytic polishing liquid with the following composition at a voltage of 10 V, a liquid temperature of 65° C., and a liquid flow rate of 3.0 m / min. The electrolytic treatment area was 0.12 m 2 .

[0410] A carbon electrode was used as the cathode, and GP0110-30R (manufactured by TAKASAGO LTD.) was used as the power source. The flow rate of the electrolyte was measured using a vortex flow monitor FLM22-10PCW (manufactured by AS ONE Corporation.).

[0411] (Electrolytic polishing liquid composition)

[0412] 85 mass% phosphoric acid (Wako Pure Chemical, Ltd. reagent) 660 mL

[0413] ·160mL pure water

[0414] · Sulfuric acid 150mL

[0415] · Ethylene glycol 30mL

[0416] <Anodizing process>

[0417] Next, the aluminum substrate after the electrolytic polishing treatment was subjected to anodizing treatment by a self-regularization method according to the procedure described in Japanese Patent Application Laid-Open No. 2007-204802.

[0418] The aluminum substrate after the electrolytic polishing treatment was subjected to a preliminary anodizing treatment for 1 hour using a 0.50 mol / L oxalic acid electrolyte at a voltage of 45 V, a liquid temperature of 16° C., and a liquid flow rate of 3.0 m / min.

[0419] Then, a film removal treatment was performed on the aluminum substrate after the preliminary anodizing treatment by immersing it in a 0.6 mol / L phosphoric acid aqueous solution (liquid temperature: 40° C.) for 0.5 hours.

[0420] Then, anodization was performed again using an electrolyte of 0.50 mol / L oxalic acid at a voltage of 45 V, a liquid temperature of 16° C., and a liquid flow rate of 3.0 m / min to partially anodize the surface of the aluminum substrate to form an anodized film with a thickness of 40 μm.

[0421] Thus, a structure having an aluminum substrate having a frame portion having a width of 5 mm at the outer edge and an anodized film provided in the frame portion of the aluminum substrate was obtained.

[0422] In addition, the pre-anodization treatment and the re-anodization treatment were both carried out in a state where the aluminum substrate was masked with a high-viscosity tape. In addition, in the pre-anodization treatment and the re-anodization treatment, the cathode was set as a titanium electrode, and the power supply used PAM320-12 (manufactured by KIKUSUI ELECTRONICS CORP.). In addition, the cooling device used NeoCool BD36 (manufactured by YamatoScientific Co., Ltd.), and the stirring and heating device used a paired stirrer PS-100 (manufactured by EYELA TOKYORIKAKIKAI CO, LTD.). In addition, the flow rate of the electrolyte was measured using a vortex flow monitor FLM22-10PCW (manufactured by AS ONE Corporation.).

[0423] <Barrier layer removal process>

[0424] Next, electrolysis treatment (electrolytic removal treatment) was performed under the same treatment solution and treatment conditions as the above-mentioned anodizing treatment, while the voltage was continuously decreased from 45 V to 0 V at a voltage drop rate of 0.2 V / sec. For the electrolysis treatment, PK45-9 (model, manufactured by Matsusada Precision Inc.) was used as a DC power supply.

[0425] After the anodized substrate is fully washed with running water, it is dried with low-temperature wind within a few minutes. After the anodized substrate is alternately immersed in ion exchange water (50°C) and a solution containing a surfactant (45°C) for 3 minutes each, the ion exchange water is drained, and then it is provided in a wet state for the barrier layer removal treatment. In addition, as a solution containing a surfactant, a solution prepared by diluting the pretreatment solution "NeutraClean68" manufactured by ROHM AND HAA S ELECTRONIC MATERIALS KK with ion exchange water in a ratio of 1:4 is used.

[0426] The etching treatment (barrier layer removal treatment) was carried out by immersion for 2 minutes in a sodium hydroxide solution containing supersaturated metal zinc maintained at a temperature of 25° C., and then the barrier layer at the bottom of the anodized film was removed by water washing and a zinc conductive layer was formed on the surface of the aluminum substrate exposed through the micropores. As the sodium hydroxide solution containing metal zinc, a solution prepared by dissolving 2000 ppm of zinc oxide in a sodium hydroxide aqueous solution (NaOH=52 g / L) was used.

[0427] Here, the average diameter of micropores (fine pores) present in the anodized film after the barrier layer removal step is 60 nm. The average diameter is obtained by taking a surface photograph (magnification 50,000 times) by FE-SEM and taking it as the average value of 50 points.

[0428] And, the average thickness of the anodized film after the barrier layer removal process is 40 μm. That is, the average thickness of the oxide film is 40 μm. In addition, the average thickness of the anodized film is calculated as follows: the anodized film is cut in the thickness direction by FIB (Focused Ion Beam), and the surface photograph of its cross section is taken by FE-SEM (50,000 times magnification) as the average value of 10 points.

[0429] The density of micropores in the anodized film is about 100 million / mm 2 The density of micropores was measured and calculated by the method described in paragraphs

[0168] and

[0169] of Japanese Patent Application Laid-Open No. 2008-270158.

[0430] And, the regularity of the micropores present in the anodized film is 92%. In addition, the regularity is measured and calculated by taking surface photos (20,000 times magnification) by FE-SEM, and by the method described in paragraphs

[0024] to

[0027] of Japanese Patent Publication No. 2008-270158.

[0431] <Metal filling process>

[0432] Next, electroplating was performed using the aluminum substrate as a cathode and copper as a positive electrode.

[0433] Specifically, constant current electrolysis is performed using a copper plating solution of the composition shown below to obtain a filled microstructure in which the inside of the micropores is filled with copper and a second metal part composed of copper is formed on the frame part. Figure 2 ) is 2 μm, and the thickness δ on the frame (reference Figure 2 ) is 5μm.

[0434] Here, the constant current electrolysis used PAS20-36 (manufactured by KIKUSUI ELECTRONICS CORP.) as a power source, a plating apparatus manufactured by Novell, Inc., and a power source (HZ-3000) manufactured by HOKUTO DENKO CORPORATION. After confirming the deposition potential by cyclic voltammetry in the plating solution, the treatment was carried out under the following conditions.

[0435] (Copper plating solution composition and conditions)

[0436] ·Copper sulfate 100g / L

[0437] ·Sulfuric acid 1g / L

[0438] ·Hydrochloric acid 15g / L

[0439] ·SPS (3,3'-dithiobis(1-propanesulfonic acid) disodium) 8.5ppm

[0440] PEG (polyethylene glycol) 5ppm

[0441] Temperature 30℃

[0442] Current density 10A / dm 2

[0443] (Example 2)

[0444] In Example 2, compared with Example 1, the treatment time of the electroplating treatment is adjusted, and the thickness γ on the sandwich portion (reference Figure 2 ) is set to 5 μm, and the thickness δ on the frame portion (reference Figure 2 ) is set to 10μm. Except for this difference, the same as Example 1.

[0445] (Example 3)

[0446] In Example 3, compared with Example 1, the treatment time of the electroplating treatment is adjusted, and the thickness γ on the sandwich portion (reference Figure 2 ) is set to 20 μm, and the thickness δ on the frame portion (reference Figure 2 ) is set to 40μm. Except for this difference, the same as Example 1.

[0447] (Example 4)

[0448] In Example 4, compared with Example 1, the treatment time of the electroplating treatment is adjusted, and the thickness γ on the sandwich portion (reference Figure 2 ) is set to 10 μm, and the thickness δ on the frame portion (reference Figure 2 ) is set to 20μm. Except for this difference, the same as Example 1.

[0449] (Example 5)

[0450] In Example 5, compared with Example 1, the treatment time of the electroplating treatment is adjusted, and the thickness γ on the sandwich portion (reference Figure 2 ) is set to 50 μm, and the thickness δ on the frame portion (reference Figure 2 ) is set to 90μm. Except for this difference, the same as Example 1.

[0451] (Example 6)

[0452] In Example 6, compared with Example 1, a circular aluminum substrate with a diameter of 15 cm is used, and masking is performed with a high-viscosity tape in a manner that can form a 5 mm wide frame around it, and the size of the internal partition portion 16 is made to have a diameter of 14 cm. Except for this difference, it is the same as Example 1.

[0453] (Comparative Example 1)

[0454] In Comparative Example 1, compared with Example 1, the treatment time of the electroplating treatment was adjusted, and the second metal part was not formed on the spacer part and the frame part, and copper was filled in the through hole of the spacer part. In Comparative Example 1, the thickness on the spacer part and the thickness on the frame part are marked as "-".

[0455] (Comparative Example 2)

[0456] In Comparative Example 2, the treatment time of the electroplating treatment was adjusted compared with Example 1, and the thickness γ on the sandwich portion (reference Figure 2 ) is set to 150 μm, and the thickness δ on the frame portion (reference Figure 2 ) is set to 200μm. Except for this difference, the same as Example 1.

[0457] [Table 1]

[0458]

[0459] As shown in Table 1, in Examples 1 to 6, better results were obtained in terms of uniformity and processability compared to Comparative Example 1, and both uniformity and processability were achieved.

[0460] In Comparative Example 1, there is no second metal portion on the spacer portion and the frame portion, and the through-holes of the spacer portion are not sufficiently filled with copper, resulting in poor uniformity and failure to achieve both uniformity and processability.

[0461] (Example 2)

[0462] Regarding the transport method, the filled microstructure of Example 1 of the first example was used to evaluate transport properties using Examples 10 to 13 and Comparative Examples 10 and 11 shown below as transport methods.

[0463] <Evaluation of transportability>

[0464] Using the filled microstructure, the transportability was evaluated as follows.

[0465] Regarding transportability, according to the general rules of JIS Z0200:2013 Packaged Goods - Performance Test Methods, the random vibration test described in JIS Z0232:2004 Packaged Goods - Vibration Test Methods was assumed to be level 1, and a transport vibration test and a bounce vibration test were performed and evaluated.

[0466] The packaging method is to sandwich the completed filled microstructure of Example 1 with cushioning paper, a protective film or a silicon wafer and seal it in a vinyl chloride box (155mm×155mm×35mm, styrene square box type 19, manufactured by AS ONE Corporation). The cushioning paper, protective film or silicon wafer have different thicknesses, so when it is cushioning paper or protective film, a cushioning material made of foamed polystyrene with a thickness of 1cm is arranged on the upper and lower sides of the stacked filled microstructure. In addition, when the filled microstructure uses cushioning paper or a protective film, 10 pieces are stacked and packaged. In the case of a silicon wafer, 3 pieces of the filled microstructure are stacked and packaged. A lid is placed on the box, and each box is laminated and packaged and used as a test material.

[0467] The temperature and humidity conditions in the transportability test are based on G (+23°C, 50% RH (relative humidity)) in Table 1 (Pretreatment temperature and humidity conditions) of JIS Z 0203:2000. The test material is subjected to a random vibration test for 180 minutes, followed by a 30-minute bounce test on the same test material.

[0468] After the above test, the first metal part and the second metal part filled with the microstructure taken out of the box were visually checked. The result of the sheet with the worst evaluation grade among the plurality of sheets conveyed was used as the overall evaluation.

[0469] The damage of the first metal portion and the damage of the second metal portion were evaluated in accordance with the following evaluation criteria for each of the first metal portion and the second metal portion. The evaluation results of the transportability are shown in Table 2 below.

[0470] Evaluation Benchmarks

[0471] ·1st Metal Division

[0472] The case where the first metal portion is not damaged is regarded as A.

[0473] The case where the first metal portion is damaged but does not reach the intervening portion (anodized film) is regarded as B.

[0474] The case where the first metal portion is damaged and reaches the intervening portion (anodized film) is regarded as C.

[0475] ·2nd Metal Division

[0476] The case where the second metal portion is not damaged is regarded as A.

[0477] The case where the second metal portion is damaged but does not reach the intervening portion (anodized film) is regarded as B.

[0478] The case where the second metal portion is damaged and reaches the intervening portion (anodized film) is regarded as C.

[0479] Hereinafter, Examples 10 to 13 and Comparative Examples 10 and 11 will be described.

[0480] (Example 10)

[0481] In Example 10, a 60 μm thick backing paper was placed on the second metal part filled with fine structures, and the filled fine structures were transported by stacking 10 sheets. AP Cleaning Paper II A4 Pink (72 g / m 2 ).

[0482] (Example 11)

[0483] In Example 11, a protective film with a thickness of 100 μm was provided on the second metal part of the filled microstructure, and the filled microstructure was transported by stacking 10 sheets. The protective film used was a No. 9492 polyethylene protective sheet (thickness 0.06 mm, manufactured by TERAOKA SEISAKUSHO CO., LTD.).

[0484] (Example 12)

[0485] In Example 12, the second metal portion of the filled microstructure is directed toward the silicon wafer, and the filled microstructure and the silicon wafer are stacked as a conveying method for stacking three filled microstructures. The silicon wafer is transported in this conveying method. A 6-inch silicon wafer that complies with the SEMI (Semiconductor Equipment and Materials International) standard is used.

[0486] (Example 13)

[0487] Compared with Example 1, Example 13 is constructed so that the frame portion is lower than the spacer portion. In the 15 cm square device produced up to the barrier layer removal step of Example 1 of the above-mentioned Example 1, a circular substrate with a diameter of 14 cm is obtained by using the central portion having an anodized film layer on the entire surface. The central portion is masked with an easily peelable tape around the circular substrate in such a way that a 2 mm wide anodized film exposed portion can be formed, and only the anodized film on the peripheral portion is dissolved and removed using an aqueous sodium hydroxide solution. Since the height difference between the frame portion and the surface of the anodized film is 40 μm, they are considered to be on approximately the same plane. Using the circular substrate with a frame portion formed around it in this way, a metal filling treatment is performed under the same conditions as in Example 1 to obtain Example 13.

[0488] In Example 13, a protective film was provided on the second metal part filled with fine structures, and the filled fine structures were transported by stacking 10 sheets. As the protective film, the same protective film as in Example 111 was used.

[0489] (Comparative Example 10)

[0490] Comparative Example 10 differs from Example 10 in that no protective layer is provided, but the conveyance was carried out in the same manner as Example 10. In addition, since Comparative Example 10 does not have a protective layer, "-" is marked in the column of the protective layer in Table 2 below.

[0491] (Comparative Example 11)

[0492] Comparative Example 11 differs from Example 13 in that no protective layer is provided, but the conveyance was performed in the same manner as Example 13. In addition, since Comparative Example 11 does not have a protective layer, "-" is marked in the column of protective layer in Table 2 below.

[0493] [Table 2]

[0494]

[0495] As shown in Table 2, in Examples 10 to 13, the protective layer was provided during transportation, and compared with Comparative Examples 10 and 11, the first metal portion and the second metal portion could be transported without being damaged.

[0496] In Comparative Examples 10 and 11, since there was no protective layer, damage reaching the intervening portion occurred in the first metal portion and the second metal portion.

[0497] Explanation of symbols

[0498] 10-filled microstructure, 11-valve metal component, 11a, 15a, 16a, 26a, 61a-surface, 11b, 16e-outer edge, 11c, 15c-region, 11e-bottom, 12, 13, 14-mask, 13a-opening, 15-first metal part, 15b-outer edge, 15d-frame part, 15e-bottom, 15f-inner surface, 15g-bottom surface, 16-sandwich part, 16b-back surface, 17-through hole, 18-structure, 19-second metal part, 20-conducting path, 20 a, 20b-protrusion, 22-resin substrate, 24-support, 26-resin layer, 27-peeling layer, 28-support layer, 29-peeling agent, 30-double-sided adhesive, 31-support member, 32-metal-filled microstructure, 40-container, 42-container body, 42a-opening, 42b-container interior, 44-lid, 45-protective layer, 50-storage bag, 51-moisture absorbent, 60-electrode body, 61-insulating support, 62-conductive layer, 63-anti-etching layer, Dt-thickness direction, h-thickness, H A -thickness, p - distance between centers, Q - area, x - direction, δ, γ - thickness.

Claims

1. A filled microstructure, comprising: a first metal part having a frame portion disposed at an outer edge; a spacer portion disposed in a region surrounded by the frame portion and having a plurality of fine holes; and a second metal portion that fills the plurality of fine holes of the sandwiching portion and directly contacts the frame portion, The first metal portion includes a metal selected from valve metals, The intervening portion includes an oxide of the metal selected from the valve metal, and the average diameter of the plurality of pores is 1 μm or less, A thickness of a portion of the second metal portion that is present on the frame portion is greater than or equal to 2 μm and less than or equal to 20 μm.

2. The filled microstructure according to claim 1, wherein The first metal portion is made of aluminum, The spacer is formed of an anodized film of the aluminum.

3. The filled microstructure according to claim 1 or 2, wherein: The second metal portion is made of copper.

4. A method of conveying, wherein: In the filled fine-structure product according to any one of claims 1 to 3, a protective layer is provided on the second metal portion, and the protective layer is stacked and transported.

Citation Information

Patent Citations

  • Method of manufacturing structure

    JP2007204802A

  • Anisotropic conductive member, and its manufacturing method

    JP2008270158A

  • Method for manufacturing microstructure

    JP2013167023A

  • Microstructures, method for producing microstructures, and optical field amplifying device

    CN101319994A

  • Method for embedding nano metal at inside and surface of anodic oxide film hole of aluminum and alloy of aluminum

    CN101660188A